Ethylene-based copolymers and propylene-alpha-olefin-diene compositions for laminar articles
By using a composition of propylene-α-olefin-diene (PEDM) terpolymer and ethylene-based copolymer, the deficiencies in EP(D)M polymers in terms of bondability and green strength are solved, and better performance adaptability is achieved.
Patent Information
- Application Number
- CN202080059532.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-17
- Filing Date
- 2020-07-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-07-17
AI Technical Summary
The existing EP(D)M polymers lack sufficient adhesion and green strength in both vulcanized and unvulcanized states, limiting their use in applications such as transmission belts.
The elastomeric compositions containing propylene-α-olefin-diene (PEDM) terpolymer and ethylene-based copolymer are used to improve the adhesion and green strength by adjusting the composition.
Improved adhesion and green strength of the composition in the unvulcanized state are achieved, improving its performance in manufacturing and end-use applications, especially in applications such as transmission belts.
Smart Images

Figure CN114286840B_ABST
Abstract
Description
[0001] Inventors: Zhifeng Bai, Scott H.Loyd, Milind B.Joshi, Felix M.Zacarias, XiaoBo.Peng, Yuya Iwashita
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims the benefit of priority to USSN 62 / 875,196, filed on July 17, 2019, entitled “ETHYLENE-BASED COPOLYMERS AND PROPYLENE-α-OLEFIN-DIENE COMPOSITIONS FOR LAMINAR ARTICLES,” which is incorporated herein by reference in its entirety. Technical Field
[0004] The present disclosure relates to polymer compositions comprising ethylene-based copolymers and propylene-alpha-olefin-diene (PEDM) terpolymers, as well as belts, hoses, and roofing and other articles comprising such blends of the copolymers and terpolymers. Background Art
[0005] Elastomeric polymer compounds, such as EP(D)M rubbers, are widely used in automotive and industrial applications (e.g., brake components, under-hood hoses, automotive radiator coolant hoses, air conditioning hoses, steam hoses, power transmission belts such as V-belts, flat belts, toothed or synchronous belts, multi-ribbed belts, and conveyor belts) for their excellent thermal and oxidative stability, and their excellent chemical resistance to polar organic and aqueous inorganic fluids.
[0006] The properties required for automotive coolant, air and heater hose, air conditioning (A / C) and brake hose formulations include high green and tear strength, good property retention after aging balanced with low temperature flexibility and compression set, and easy mixing and processing. Belts, such as power transmission belts and conveyor belts, have similar requirements. EP(D)M elastomers provide these properties and have been widely accepted as the reliable material of choice for a wide range of applications, such as general purpose hoses, heat resistant hoses, high heat resistant hoses, transmission belts, conveyor belts, etc.
[0007] Power transmission belts include V-belts, flat belts, toothed or synchronous belts, and multi-ribbed belts. The belt construction typically includes an elastomeric belt body, a tension cord or other textile tensile member embedded in the belt body or spirally wound, and other textile reinforcements that are usually embedded in the belt body or cover one or more of the belt surfaces.
[0008] The elastomeric belt body may include one or more vulcanized rubber compositions, or elastomeric compositions, such as thermoplastic elastomer compositions. Elastomeric compositions traditionally include ethylene-propylene-(optionally diene) polymers, referred to as EP(D)M polymers or EP(D)M rubbers. Elastomeric compositions based on EP(D)M polymers need to have a suitable combination of processability and physical properties in both the vulcanized and unvulcanized states to meet manufacturing and end-use application requirements.
[0009] Two noteworthy properties currently lacking in the vulcanized EP(D)M compositions of compositions for drive belt applications are adhesion and green strength, and particularly the balance between the two. Adhesion (also known as rubber-to-rubber adhesion, construction adhesion or green adhesion) is the force required to separate two identical samples of a composition (e.g., a rubber sample) or a rubber specimen from another substrate such as a fabric, while green strength is the tensile modulus measured at 25% or other extension of a sample of a composition (e.g., a rubber specimen). As used herein, "green" modifies the term and means uncured.
[0010] From a manufacturing perspective, for unvulcanized EP(D)M compositions, the uncured elastomeric sheet coming out of the calender rolls should have sufficient cohesiveness to maintain intimate contact and adhesion of rubber to rubber and other reinforcing elements (e.g., fabric) during processing prior to curing, and to allow individual sheets to be spliced to form a sheet several times wider than the width of the calendered sheet as it leaves the rolls. The unvulcanized elastomer should also have sufficient green strength to be rolled onto a mandrel without sagging. However, it has been found that EP(D)M polymers have insufficient cohesiveness and possible green strength, which limits their use as (and in the manufacture of) transmission belts.
[0011] Adhesiveness and green strength are affected by the crystallinity of polymer. The lower the crystallinity, the greater the adhesiveness. For example, the adhesiveness of EP (D) M compositions can be changed by reducing the ethylene content of EP (D) M polymers and thereby reducing the crystallinity. However, lower crystallinity reduces green strength. In addition, lower crystallinity is usually unfavorable for performances such as tensile strength, tear resistance and abrasion resistance, which are also important properties of transmission belts. For conveyor belts, hoses, roofs and other EP (D) M applications, there is also a similar demand for better balancing of better adhesiveness or adhesiveness and green strength. In fact, design has these distinct polymer features to meet the single polymer (or polymer composition) required for adhesiveness and green strength and has proposed a challenge in producing an acceptable polymer synthesis method.
[0012] Hydrocarbon tackifiers have been used as additives in EP(D)M compositions to enhance adhesion. However, non-hydrogenated tackifiers co-vulcanize with EP(D)M but do not exhibit long-term heat resistance due, at least in part, to their unsaturation. Hydrogenated tackifiers exhibit better thermal stability; however, since they are not crosslinked with EP(D)M, they are more expensive and may be detrimental to cure and mechanical properties. Furthermore, tackifying resins directionally increase EP(D)M compound costs when introduced as an additive rather than replacing the EP(D)M polymer component.
[0013] Some potentially relevant background references include: WIPO Publication Nos. WO 2016 / 053541, WO 2016 / 053542, WO 2016 / 114914; U.S. Patent Nos. 5,654,370; 5,571,868; 7,199,189; 7,390,866; 7,605,217; 7,867,433; 7,928,165; 8,013,093; 8,765,832; and 8,841,383; U.S. Patent Publication No. 2013 / 050488; and JR Beatty, Rubber Chem. & Tech., 42, 1041 (1969) and GR Hamed, Rubber Chem. & Tech., 54, 578 (1981).
[0014] There is a need for polymers and polymer compositions having adequate adhesion and green strength for use in tapes, hoses, and roofing. Summary of the invention
[0015] Embodiments of the present disclosure include elastomeric compositions comprising a propylene-α-olefin-diene (PEDM) terpolymer and, optionally, an ethylene-based copolymer (e.g., EP(D)M). The PEDM terpolymers described herein may comprise 70 wt% to 92.5 wt% propylene, 7.5 wt% to 30 wt% C2 or C4-C12 α-olefin, and 3.5 wt% to 20 wt% diene, the wt% being based on the weight of the PEDM terpolymer, and the PEDM terpolymer may have a Mooney viscosity (ML(1+4)) of 25 MU to 100 MU.
[0016] In one aspect, an elastomeric composition is provided comprising 1 to 100 parts by weight per 100 parts by weight of rubber (phr) of a first propylene-α-olefin-diene (PEDM) terpolymer comprising 70 wt% to 92.5 wt% propylene, 7.5 wt% to 30 wt% C2 or C4-C12 α-olefin, and 3.5 wt% to 20 wt% diene, the wt% based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML(1+4)) of 25 MU to 100 MU; and optionally, 0 to 99 phr of an ethylene-based copolymer comprising 40 wt% to 95 wt% ethylene, 0 wt% to 10 wt% one or more dienes, and 5 wt% to 60 wt% C3-C12 α-olefin, the wt% based on the total weight of the ethylene-based copolymer.
[0017] In another aspect, an elastomeric composition is provided, comprising 1 to 30 parts by weight per 100 parts by weight of rubber (phr) of a propylene-α-olefin-diene (PEDM) terpolymer, the propylene-α-olefin-diene (PEDM) terpolymer comprising 70 wt% to 92.5 wt% propylene, 7.5 wt% to 30 wt% C2 or C4-C12 α-olefin, and 0.5 wt% to 3.4 wt% diene, the wt% being based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML(1+4)) of 10 MU to 100 MU; and 70 to 99 phr of an ethylene-based copolymer, the ethylene-based copolymer comprising 40 wt% to 95 wt% ethylene, 0 wt% to 10 wt% of one or more dienes, and 5 wt% to 60 wt% C3-C12 α-olefin, the wt% being based on the total weight of the ethylene-based copolymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a fragmentary perspective view of a drive belt according to some embodiments of the present disclosure.
[0020] Figure 2 is a fragmentary perspective view of a drive belt according to another embodiment of the present disclosure.
[0021] Figure 3 is a fragmentary perspective view of a drive belt according to yet another embodiment of the present disclosure.
[0022] Figure 4 An exemplary conveyor belt construction is shown including, in order, (a) a cover rubber layer, (b) alternating fabric and rubber skin layers, and (c) a bottom rubber layer 408 .
[0023] Figure 5 An exemplary hose construction is shown, which includes, in sequence, (a) an inner rubber tube, (b) a reinforcing fabric, and (c) an outer rubber layer.
[0024] Detailed Description
[0025] Embodiments of the present disclosure include compositions containing PEDM terpolymers and optionally, ethylene-based copolymers. It has been found that the compositions of the present disclosure provide improved green adhesion, adhesion aging, and green strength. These improved properties provide hoses, roofing, and belts, such as conveyor or transmission belts, with improved performance for better use and improved manufacture of hoses, roofing, and belts.
[0026] definition
[0027] The term "copolymer" as used herein refers to a polymer including two or more monomers. The term "polymer" as used herein includes, but is not limited to, homopolymers, copolymers, terpolymers, etc. and their alloys and blends. The term "terpolymer" as used herein refers to a polymer synthesized from three different monomers. In some embodiments, the terpolymer can be prepared as follows: (1) all three monomers are mixed at the same time or (2) different comonomers are introduced sequentially. The mixing of comonomers can be carried out in one, two or possibly three different reactors in series and / or parallel. The term "polymer" as used herein also includes impact, block, grafted, random, gradient and alternating copolymers. The term "polymer" should also include components of all possible geometric shapes, unless otherwise specifically stated. Such configurations can include isotactic, syndiotactic and random (i.e., atactic) symmetric.
[0028] The term "blend" as used herein refers to a mixture of two or more polymers. The blend can be prepared, for example, by solution blending, melt mixing, or compounding in a shear mixer. Solution blending is commonly used to prepare adhesive formulations comprising baled butyl rubber, a tackifier, and an oil. The solution blend is then applied to a fabric substrate and the solvent evaporated to leave the adhesive.
[0029] As used herein, the term "monomer" or "comonomer" can refer to the monomer used to form the polymer (i.e., the unreacted chemical in its prior form to polymerization) and can also refer to the monomer after it has been incorporated into the polymer (also referred to herein as a "[monomer]-derived unit"). Various monomers are discussed herein, propylene monomers, ethylene monomers, and diene monomers.
[0030] The term "ethylene-based copolymer" as used herein includes copolymers derived from ethylene, alpha-olefins containing 3 or more carbon atoms (e.g., 3-12 carbon atoms or 6-10 carbon atoms), and optionally, dienes. In a preferred embodiment, the ethylene-based copolymer is an ethylene-propylene copolymer or an ethylene-propylene-diene polymer.
[0031] As used herein, "ethylene-propylene-diene polymer" (EP(D)M) is defined as a copolymer having an ethylene content (derived from ethylene monomers) and a propylene content (derived from propylene monomers) and, optionally, a diene content (derived from diene monomers, preferably non-conjugated diene monomers). The ethylene content can be from 40 wt% to 95 wt% (e.g., from 41 wt% to 95 wt%, or from 45 wt% to 90 wt%, or from 50 wt% to 80 wt%), the diene content is from 0 wt% to 10 wt%, and the remainder (i.e., the remaining wt% of the polymer) is primarily (e.g., allowing for small amounts of impurities) or entirely propylene content, based on the weight of the polymer. The EP(D)M can have a Mooney viscosity, (ML, 1+4@125°C) of 15 to 100 (measured according to ASTM D1646-17). The terms "EP(D)M" and "EPDM" are used interchangeably and have the same meaning, unless the context dictates otherwise (e.g., when the polymer is referred to as finally comprising diene monomer(s)).
[0032] As used herein, the term "propylene-α-olefin-diene terpolymer" includes polymers derived from propylene, α-olefin (most preferably ethylene) and diene monomers. The propylene-α-olefin-diene terpolymer may be referred to as PEDM for short, even if an α-olefin replacing or supplementing ethylene is considered as a comonomer in such a terpolymer, and / or a polyene replacing or supplementing the diene is considered. Preferably, the PEDM terpolymer comprises 70 wt% to 97.5 wt% (e.g., 60 wt% to 89 wt%, or 85 wt% to 95 wt%) propylene content (derived from propylene monomer), 2.5 wt% to 30 wt% (e.g., 2.5 wt% to 20 wt%, or 7.5 wt% to 30 wt%) ethylene content (derived from ethylene monomer) and 0.5 wt% to 10 wt% (e.g., 3.5 wt% to 10 wt%, or 2.5 wt% to 7 wt%) diene content (derived from diene monomer).
[0033] As used herein, "phr" means parts per 100 parts of rubber, where "rubber" is the total rubber content of the composition. Herein, both PEDM and ethylene-based copolymers (e.g., EP(D)M) are considered to contribute to the total rubber content, so that in a composition in which both are present, the "total rubber" is the total weight of the PEDM and ethylene-based copolymers. Thus, for example, a composition having 30 parts by weight of PEDM and 70 parts by weight of ethylene-based copolymers can be referred to as having 30 phr PEDM and 70 phr ethylene-based copolymers. Other components added to the composition are calculated based on phr. For example, adding 50 phr of oil to the composition means that for every 100 g of PEDM and ethylene-based copolymer combined, 50 g of oil is present in the composition. Unless otherwise specified, phr should be taken as phr by weight.
[0034] As used herein, "tensile strength" refers to the amount of stress applied to a sample to cause the sample to break. It can be expressed in Pascals or pounds per square inch (PSI). ASTM D412-16 can be used to determine the tensile strength of a polymer.
[0035] As used herein, "Mooney viscosity" is the Mooney viscosity of a polymer or polymer composition. The polymer composition analyzed for the determination of Mooney viscosity should be substantially free of solvent. For example, the sample can be placed on a boiling water steam table in a hood to evaporate most of the solvent and unreacted monomers, and then dried overnight (12 hours, 90°C) in a vacuum oven according to laboratory analytical techniques before testing, or the test sample can be obtained from the devolatilized polymer (i.e., the polymer after devolatilization in an industrial scale process). Unless otherwise stated, the Mooney viscosity is measured using a Mooney viscometer according to ASTM D1646-17, but the following modifications / clarifications are made to the procedure. First, the sample polymer is pressed between two hot plates of a compression molding press before testing. The plate temperature is 125°C + / - 10°C instead of 50 + / - 5°C recommended in ASTM D1646-17, because 50°C does not cause sufficient densification. In addition, although ASTM D1646-17 allows some options for die protection, if the two options provide conflicting results, PET 36 microns should be used as die protection. Additionally, ASTM D1646-17 does not indicate sample weight in paragraph 8; therefore, to the extent that results may vary based on sample weight, the Mooney viscosity determined in paragraph 8 of ASTM D1646-17 using a sample weight of 21.5 + / - 2.7 g will be used as the standard. Finally, the remaining procedures given in paragraph 8 of D1646-17 prior to testing are 30 minutes at 23 + / - 3°C in air; the Mooney values reported herein are determined after 30 minutes of standing in air at 24 + / - 3°C. The samples are placed on either side of the spindle according to the ASTM D1646-17 test method; the torque required to turn the viscometer spindle at 2 rpm is measured by the sensor that determines the Mooney viscosity. Results are reported as Mooney units (ML, 1+4@125°C), where M is the Mooney viscosity number, L represents the large rotor (defined as ML in ASTM D1646-17), 1 is the warm-up time (in minutes), 4 is the sample run time after the motor is started (in minutes), and 125°C is the test temperature. Thus, a Mooney viscosity of 90 measured by the method described above would be reported as a Mooney viscosity of 90MU (ML, 1+4@125°C). Alternatively, the Mooney viscosity may be reported as 90MU; in such cases, unless otherwise stated, it should be considered that such viscosity was measured using the method just described. In some cases, a lower test temperature (e.g., 100°C) may be used, in which case the Mooney is reported as Mooney viscosity (ML, 1+4@100°C), or @T°C, where T is the test temperature.
[0036] The terms "hydrocarbyl radical", "hydrocarbyl" and "hydrocarbyl group" are used interchangeably throughout the document. Likewise, the terms "group", "radical" and "substituent" are also used interchangeably in this document. For the purposes of this disclosure, a "hydrocarbyl group" is defined as a group containing hydrogen atoms and up to 50 carbon atoms, and which may be linear, branched or cyclic, and when cyclic, may be aromatic or non-aromatic.
[0037] A substituted hydrocarbon group is a group in which at least one hydrogen atom has been replaced by at least one functional group, such as NR x 2. OR x , SeR x 、TeR x , PR x 2. AsR x 2. SbR x 2. SR x , BR x or wherein at least one non-hydrocarbon atom or group has been inserted into the hydrocarbon group, such as -O-, -S-, -Se-, -Te-, -N(R x )-、=N-、-P(R x )-、=P-、-As(R x )-、=As-、-Sb(R x )-、=Sb-、-B(R x )-, =B-, etc., where R x are independently a hydrocarbon group or a halocarbyl group, and two or more R x Can be linked together to form substituted or unsubstituted saturated, partially unsaturated or aromatic cyclic or polycyclic ring structures. Examples of substituted hydrocarbon groups include -CH2CH2-O-CH3 and -CH2-NMe2, wherein the groups are bonded via carbon atoms, but do not include groups wherein the groups are bonded via heteroatoms, such as -OCH2CH3 or -NMe2.
[0038] A silylcarbyl group is a group in which one or more hydrocarbyl hydrogen atoms have been substituted with at least one SiR*3-containing group or in which at least one -Si(R*)2- has been inserted into the hydrocarbyl group, wherein R* is independently a hydrocarbyl group or a halogenated hydrocarbyl group, and two or more R* may be combined together to form a substituted or unsubstituted saturated, partially unsaturated or aromatic cyclic or polycyclic ring structure.
[0039] Substituted silyl hydrocarbon groups are groups in which at least one hydrogen atom has been replaced by at least one functional group such as -NR*2, -OR*, -SeR*, -TeR*, -PR*2, -AsR*2, -SbR*2, -SR*, -BR*2, -GeR*3, -SnR*3, -PbR*3, etc., or groups in which at least one non-hydrocarbon atom or group has been inserted into the silyl hydrocarbon group, such as -O-, -S-, -Se-, -Te-, -N(R*)-, =N-, -P(R*)-, =P-, -As(R*)-, =As-, -Sb(R*)-, =Sb-, -B(R*)-, =B-, -Ge(R*) 2- , -Sn(R*)2-, -Pb(R*)2-, etc., wherein R* is independently a hydrocarbon group or a halogenated hydrocarbon group, and two or more R* can be joined together to form a substituted or unsubstituted saturated, partially unsaturated or aromatic cyclic or polycyclic ring structure. The substituted silyl hydrocarbon group is bonded only via carbon or silicon atoms.
[0040] Germylcarbyl is a group in which one or more hydrocarbyl hydrogen atoms have been substituted with at least one group containing GeR*3 or in which at least one -Ge(R*)2- has been inserted into the hydrocarbyl, wherein R* is independently a hydrocarbyl or a halogenated hydrocarbyl, and two or more R* may be combined together to form a substituted or unsubstituted saturated, partially unsaturated or aromatic cyclic or polycyclic ring structure. Substituted germylcarbyl is bonded only via carbon or germanium atoms.
[0041] Substituted germyl hydrocarbon groups are groups in which at least one hydrogen atom has been replaced by at least one functional group such as -NR*2, -OR*, -SeR*, -TeR*, -PR*2, -AsR*2, -SbR*2, -SR*, -BR*2, -SiR*3, -SnR*3, -PbR*3, etc., or groups in which at least one non-hydrocarbon atom or group has been inserted into the germyl hydrocarbon group, such as -O-, -S-, -Se-, -Te-, - N(R*)-, =N-, -P(R*)-, =P-, -As(R*)-, =As-, -Sb(R*)-, =Sb-, -B(R*)-, =B-, -Si(R*)2-, -Sn(R*)2-, -Pb(R*)2-, etc., wherein R* is independently a hydrocarbon group or a halogenated hydrocarbon group, and two or more R* can be joined together to form a substituted or unsubstituted saturated, partially unsaturated or aromatic cyclic or polycyclic ring structure.
[0042] A halohydrocarbyl group is a group in which one or more of the hydrocarbyl hydrogen atoms has been replaced by at least one halogen (eg, F, Cl, Br, I) or a halogen-containing group (eg, CF3).
[0043] Substituted haloalkyl is a group in which at least one haloalkyl hydrogen or halogen atom has been replaced by at least one functional group such as NR*2, OR*, SeR*, TeR*, PR*2, AsR*2, SbR*2, SR*, BR*2, etc. or in which at least one non-carbon atom or group has been inserted into the haloalkyl group, such as -O-, -S-, -Se-, -Te-, -N(R*)-, =N-, -P(R*)-, =P-, -As(R*)-, =As-, -Sb(R*)-, =Sb-, -B(R*)-, =B-, etc., wherein R* is independently a hydrocarbon group or a haloalkyl group, provided that at least one halogen atom remains on the original haloalkyl group. In addition, two or more R* can be joined together to form a substituted or unsubstituted saturated, partially unsaturated, or aromatic cyclic or polycyclic ring structure. Substituted haloalkyl is bonded only via carbon atoms.
[0044] Heteroatoms are atoms other than carbon or hydrogen.
[0045] The term "aryl" or "aryl group" refers to monocyclic or polycyclic aromatic rings and substituted variants thereof, including but not limited to phenyl, naphthyl, 2-methyl-phenyl, benzyl, 4-bromo-benzyl. Likewise, "heteroaryl" refers to an aryl group in which a ring carbon atom (or two or three ring carbon atoms) has been replaced by a heteroatom such as N, O or S. The term "substituted aryl" refers to: 1) an aryl group in which a hydrogen has been replaced by a substituted or unsubstituted hydrocarbon group, a substituted or unsubstituted halohydrocarbon group, a substituted or unsubstituted silylhydrocarbon group or a substituted or unsubstituted germylhydrocarbon group. The term "substituted heteroaryl" refers to: 1) a heteroaryl group in which a hydrogen has been replaced by a substituted or unsubstituted hydrocarbon group, a substituted or unsubstituted halohydrocarbon group, a substituted or unsubstituted silylhydrocarbon group or a substituted or unsubstituted germylhydrocarbon group.
[0046] For nomenclature purposes, the following numbering scheme is used for indenyl, tetrahydro-s-indacenyl, and tetrahydro-as-indacenyl ligands.
[0047]
[0048] As used herein, Mn is the number average molecular weight, Mw is the weight average molecular weight, Mz is the z average molecular weight, wt% is the weight percentage, and mol% is the mole percentage. Molecular weight distribution (MWD) (also known as polydispersity) is defined as Mw divided by Mn. Unless otherwise specified, all molecular weight units (e.g., Mw, Mn, Mz) are g / mol.
[0049] The following abbreviations may be used herein: Me is methyl, Et is ethyl, Pr is propyl, cPr is cyclopropyl, nPr is n-propyl, iPr is isopropyl, Bu is butyl, nBu is n-butyl, iBu is isobutyl, sBu is sec-butyl, tBu is tert-butyl, Oct is octyl, Ph is phenyl, Bn is benzyl, Cp is cyclopentadienyl, Ind is indenyl, Flu is fluorenyl, and MAO is methylaluminoxane.
[0050] For purposes of this disclosure, a "catalyst system" is a combination of at least one catalyst compound, at least one activator, an optional co-activator, and an optional support material. For purposes of this disclosure, when a catalyst system is described as comprising neutral stable forms of components, it will be understood by those skilled in the art that the ionic forms of the components are the forms that react with monomers to produce polymers. For purposes of this disclosure, a "catalyst system" includes both neutral and ionic forms of the components of the catalyst system, such as catalyst compounds.
[0051] In the description herein, the catalyst may be described as a catalyst precursor, a procatalyst, a procatalyst compound, a metallocene catalyst compound, a metallocene catalyst, or a transition metal compound and these terms are used interchangeably.
[0052] Metallocene catalysts are defined as organometallic transition metal compounds having at least one π-bonded cyclopentadienyl moiety (or substituted cyclopentadienyl moiety) bonded to a transition metal.
[0053] For the purposes of this disclosure relating to metallocene catalyst compounds, the term "substituted" means that one or more hydrogen atoms have been replaced with a hydrocarbyl, a heteroatom (e.g., a halide), or a heteroatom-containing group (e.g., a silyl hydrocarbyl, a germyl hydrocarbyl, a halohydrocarbyl, etc.). For example, methylcyclopentadiene (Cp) is a Cp group substituted with a methyl group. Two or more adjacent hydrogen atoms may be replaced by hydrocarbyl groups to form a polycyclic cyclopentadienyl moiety, e.g., indenyl, fluorenyl, tetrahydro-s-indacenyl, etc.
[0054] For the purposes of this disclosure, "alkoxide" includes groups in which the alkyl group is C1-C 10 The alkyl group may be a linear, branched or cyclic alkyl group. The alkyl group may be a saturated or unsaturated alkyl group. In some embodiments, the alkyl group may contain at least one aromatic group.
[0055] Numerical ranges used herein include the values recited in the range. For example, a numerical range of "1 wt % to 10 wt %" includes 1 wt % and 10 wt % within the recited range.
[0056] Composition
[0057] The compositions of the present disclosure include one or more PEDM terpolymers and, optionally, one or more ethylene-based copolymers. In some embodiments, the compositions of the present disclosure include a certain amount (e.g., 1 phr to 100 phr of the composition) of PEDM terpolymers and, optionally, a certain amount (e.g., 0 phr to 99 phr of the composition) of ethylene-based copolymers. The compositions of the present disclosure may include one or more PEDM terpolymers in an amount of 1 phr to 100 phr. Other examples of the amount of one or more PEDM terpolymers suitable for use include: 1 phr to 75 phr, 1 phr to 50 phr, 1 phr to 40 phr, 3 phr to 40 phr, 5 phr to 40 phr, or 10 phr to 30 phr, wherein the remainder to 100 phr is the one or more ethylene-based copolymers.
[0058] PEDM terpolymer
[0059] The compositions described herein may include a single PEDM terpolymer or a mixture of two or more PEDM terpolymers (e.g., a dual reactor product or a physical blend). In some cases, for the sake of clarity, the PEDM terpolymers may be referred to as "a first PEDM terpolymer" and a "second PEDM terpolymer." However, it should be understood that simply because a "first PEDM terpolymer" is mentioned, it is not implied or intended to indicate that a "second PEDM terpolymer" must be present in the composition unless so stated. In addition, the PEDM terpolymers of the compositions of the present disclosure may also be classified into at least 2 categories based on their composition. In the present disclosure, for the sake of greater clarity, the names PEDM-1 and PEDM-2 are used. The compositional features of the PEDM-1 and PEDM-2 terpolymers will be described in more detail herein. The compositions of the present disclosure may further include a mixture of the PEDM-1 terpolymer, optionally with one or more PEDM-2 terpolymers.
[0060] In an example, the PEDM-1 terpolymer of the present disclosure may have a polyene (preferably diene) content of 3.5 wt % to 20 wt %, a C2 or C4 to C 12 α-olefin (preferably ethylene) content and propylene content of 70 wt% to 92.5 wt%, the wt% being based on the weight of the PEDM-1 terpolymer.
[0061] The PEDM-1 terpolymer of the present disclosure contains 70 wt% to 92.5 wt% propylene, based on the weight of the PEDM-1 terpolymer. Other preferred ranges of propylene content include 70 wt% to 91.5 wt%, or 70 wt% to 89.9 wt%, or 70 wt% to 79 wt%, or 75 wt% to 79 wt%, based on the weight of the PEDM-1 terpolymer.
[0062] The PEDM-1 terpolymer of the present disclosure contains 7.5 wt% to 30 wt% of C2 or C4-C 12 α-olefin comonomer (preferably ethylene) based on the weight of the first PEDM terpolymer. Other preferred ranges of α-olefin (e.g., ethylene) content include 8.5 wt% to 30 wt%, or 10.1 wt% to 30 wt%, or 21 wt% to 30 wt%, or 21 wt% to 25 wt%, based on the weight of the PEDM-1 terpolymer. C2 or C4 to C 12 α-olefin comonomers include, but are not limited to, ethylene, butene, pentene, hexene, heptene, octene, nonene, decene, undecene, dodecene, and branched isomers thereof. Ethylene is particularly preferred.
[0063] The PEDM-1 terpolymer of the present disclosure comprises a polyene content (preferably a diene content, based on the weight of the PEDM-1 terpolymer) of 3.5 wt% to 20 wt%, 3.5 wt% to 10 wt%, or 4 wt% to 10 wt%, or 4 wt% to 8 wt%, or 4 wt% to 6 wt%. In at least one embodiment, the diene is a 5-ethylidene-2-norbornene content in an amount of 3.5 wt% to 20 wt%, 3.5 wt% to 10 wt%, or 4 wt% to 10 wt%, or 4 wt% to 8 wt%, or 4 wt% to 6 wt%, based on the weight of the PEDM-1 terpolymer.
[0064] In an example, the PEDM-2 terpolymer of the present disclosure may have a polyene (preferably diene) content of 0.5 wt % to 7.5 wt %, a C2 or C4 to C 12 α-olefin (preferably ethylene) content and propylene content of 93 wt% to 99 wt%, said wt% being based on the weight of said PEDM-2 terpolymer.
[0065] The PEDM-2 terpolymer of the present disclosure comprises 93 wt% to 99 wt% propylene, based on the weight of the PEDM-2 terpolymer. Other preferred ranges of propylene content include 93 wt% to 98 wt%, or 93 wt% to 97 wt%, or 94 wt% to 97 wt%, or 94 wt% to 96 wt%, based on the weight of the PEDM-2 terpolymer.
[0066] The PEDM-2 terpolymer of the present disclosure contains 1 wt % to 7 wt % of C2 or C4 to C 12 α-olefin comonomer (preferably ethylene), based on the weight of the PEDM-2 terpolymer. Other preferred ranges of α-olefin (e.g., ethylene) content include 2 wt% to 7 wt%, or 3 wt% to 7 wt%, or 4 wt% to 7 wt%, or 4 wt% to 6 wt%, based on the weight of the PEDM-2 terpolymer. C2 or C4 to C 12 α-olefin comonomers include, but are not limited to, ethylene, butene, pentene, hexene, heptene, octene, nonene, decene, undecene, dodecene, and branched isomers thereof. Ethylene is particularly preferred.
[0067] The PEDM-2 terpolymers of the present disclosure comprise a polyene content (preferably a diene content) of 0.5 wt% to 7.5 wt%, or 1 wt% to 7.5 wt%, or 2 wt% to 7.5 wt%, or 2 wt% to 6 wt%, or 2 wt% to 4 wt%, based on the weight of the PEDM-2 terpolymer. In at least one embodiment, the diene is a 5-ethylidene-2-norbornene content in an amount of 0.5 wt% to 7.5 wt%, or 1 wt% to 7.5 wt%, or 2 wt% to 7.5 wt%, or 2 wt% to 6 wt%, or 2 wt% to 4 wt%, based on the weight of the PEDM-2 terpolymer.
[0068] wt% of C2, C3-C 16 The wt% of olefins and the wt% of dienes can be determined by 13 C NMR and in some cases, by 1 H NMR measurements. The wt% values in this document are uncorrected values, where the wt% of C2 is added to the wt% of C 3- C 16 The weight percent of olefins is equal to 100% unless otherwise indicated.
[0069] For ethylene-propylene and ethylene-propylene-diene copolymers, ethylene and diene content (when present) are typically measured using FTIR using ASTM D3900 and ASTM D6047. The former provides uncorrected C2 wt% values.
[0070] The corrected wt% of C2 can be calculated from the uncorrected wt% C2 using the following equation:
[0071] Corrected wt.% C2 = [Uncorrected wt.% C2 x (100 - wt.% Diene)] / 100
[0072] The wt% of ethylene and the wt% of diene therein are determined by FTIR or by NMR methods.
[0073] When C3-C 16 When the olefin is propylene, ASTM D3900 is used to determine the propylene content. When the diene is ENB, ASTM D6047 is used to determine the ENB content. If the IR method established by ASTM is not available for other C3-C 16 Olefins and / or other dienes, you can use 13 C NMR.
[0074] For the purposes of this disclosure, ethylene, C3-C 16 The mole fractions of olefins and dienes were calculated using the following equations A, B, and C, respectively:
[0075] Equation (A):
[0076]
[0077] Equation (B):
[0078]
[0079] Equation (C):
[0080]
[0081] Where "Mw(C2)" is the molecular weight of ethylene in g / mol, "Mw(C3-C 16 Olefins) are C3-C 16 The molecular weight of the olefin, "Mw(diene)" is the molecular weight of the diene in g / mol, and "wt% C2" is the corrected wt% C2.
[0082] As described above, the polyene used in the PEDM-1 and PEDM-2 terpolymers is preferably (but not necessarily) a diene. Suitable dienes may be conjugated or non-conjugated. Preferably, the diene is a non-conjugated diene. Dienes include, but are not limited to, 5-ethylidene-2-norbornene (ENB); 1,4-hexadiene; 5-methylene-2-norbornene (MNB); 1,6-octadiene; 5-methyl-1,4-hexadiene; 3,7-dimethyl-1,6-octadiene; 1,3-cyclopentadiene; 1,4-cyclohexadiene; vinyl norbornene (VNB); dicyclopentadiene (DCPD) and combinations thereof. Preferably, the diene is ENB or VNB.
[0083] The PEDM terpolymers of the present disclosure may have a weight average molecular weight (Mw) of 5,000,000 or less, a number average molecular weight (Mn) of 3,000,000 or less, and / or a z-average molecular weight (Mz) of 10,000,000 or less. In embodiments having a mixture of PEDM terpolymers, the molecular weight distribution of the PEDM terpolymers may have two or more modes (e.g., bimodal). The distribution and moments of molecular weights (number average molecular weight (Mn), weight average molecular weight (Mw), and z-average molecular weight (Mz), Mw / Mn, etc.) may be determined by using gel permeation chromatography (GPC).
[0084] The PEDM terpolymers of the present disclosure may have an Mw of 5,000 g / mol to 5,000,000 g / mol, or 10,000 g / mol to 1,000,000 g / mol, or 20,000 g / mol to 500,000 g / mol, or 50,000 g / mol to 400,000 g / mol. The PEDM terpolymers may have an Mn of 2,500 g / mol to 2,500,000 g / mol, or 5,000 g / mol to 500,000 g / mol, or 10,000 g / mol to 250,000 g / mol, or 25,000 g / mol to 200,000 g / mol. The PEDM terpolymer can have an Mz of 10,000 g / mol to 7,000,000 g / mol, or 50,000 g / mol to 1,000,000 g / mol, or 80,000 g / mol to 700,000 g / mol, or 100,000 g / mol to 500,000 g / mol. In embodiments having a mixture of PEDM terpolymers, the molecular weight distribution of the PEDM terpolymer can have two or more modes (e.g., bimodal), wherein each mode is characterized by one of the aforementioned Mw, Mn, and / or Mz values.
[0085] The molecular weight distribution index (MWD = (Mw / Mn)) of the PEDM terpolymer of the present disclosure can be from 1.5 to 40. For example, the PEDM terpolymer can have a MWD of 1.5 to 40, or 1.8 to 20, or 2.0 to 10, or 2.0 to 5, or 3 to 4.5. In one or more embodiments, the MWD of the PEDM terpolymer is from 1.8 to 5, or 1.8 to 3. For the purposes of this disclosure, Mw, Mn, and Mz will be defined as measured by a LS detector.
[0086] The PEDM terpolymers of the present disclosure may have a Mw / Mn ratio of 1.5 to 3.5, or 1.5 to 2.5, or 1.75 to 2.25.
[0087] The PEDM terpolymer of the present disclosure may have a 0.85 g / cm 3 Up to 0.92g / cm 3 , or 0.87 g / cm 3 Up to 0.90g / cm 3 , or 0.88 g / cm 3 Up to 0.89g / cm 3 The density is measured at room temperature according to ASTM D1505-10 test method.
[0088] The PEDM terpolymer of the present disclosure may have a melt flow rate (MFR, 2.16 kg weight, 230° C.) measured according to ASTM D1238-13 equal to or greater than 0.1 g / 10 min. For example, the MFR (230° C., 2.16 kg) of the PEDM terpolymer of the present disclosure may be 0.1 g / 10 min to 10 g / 10 min, or 0.1 g / 10 min to 5 g / 10 min, or 1 g / 10 min to 7 g / 10 min, or 5 g / 10 min to 10 g / 10 min.
[0089] The PEDM terpolymers of the present disclosure may have a Mooney viscosity (ML, 1+4@125°C) of 10MU to 100MU, or 10MU to 40MU, or 10MU to 60MU, or 20MU to 60MU, or 25MU to 80MU, or 30MU to 100MU. In some cases, the PEDM-1 terpolymer has a Mooney viscosity of 25MU to 100MU, or 30MU to 100MU, or 35MU to 100MU, or 41MU to 100MU, or 50MU to 100MU, or 61MU to 100MU. The PEDM-2 terpolymer may have a Mooney viscosity of 10MU to 50MU, or 10MU to 40MU, or 10MU to 30MU, or 10MU to 20MU.
[0090] The PEDM terpolymers of the present disclosure may have a heat of fusion (Hf) of less than 1 J / g. In at least one embodiment, the PEDM terpolymer is amorphous. Additionally or alternatively, the PEDM terpolymer may have atactic propylene sequences. In at least one embodiment, the PEDM terpolymer has a glass transition temperature (Tg) of -45°C to -2°C, or -35°C to -30°C. In at least one embodiment, the PEDM terpolymer may have a Hf of less than 1 J / g and syndiotactic r diads, wherein the percentage of r diads is low enough to still be substantially amorphous (i.e., have a low Hf). f The Tg and Tg can be determined by differential scanning calorimetry (DSC).
[0091] The PEDM terpolymers of the present disclosure preferably have atactic polypropylene sequences. In addition or as an alternative, they are preferably amorphous, meaning that they will show no melting peak when subjected to differential scanning calorimetry (DSC) testing. Alternatively, the PEDM according to some embodiments may show a minor melting peak, such that they may be observed to have Hf<1 J / g according to the DSC method described herein. In addition, when the PEDM shows any melting peak, such peak may be a single peak, or the PEDM may show secondary melting peaks adjacent to the main peak. For purposes of this article, these secondary melting peaks are collectively considered as a single melting point, wherein the highest peak among these peaks (relative to the baseline described herein) is considered to be the melting point of the PEDM terpolymer.
[0092] According to yet another embodiment, the crystallinity of the PEDM terpolymer may be expressed in terms of a percentage of crystallinity (i.e., % crystallinity), as determined according to the DSC procedure described herein. While the PEDM according to certain embodiments is amorphous (and may therefore be said to have 0% crystallinity), if the PEDM according to various other embodiments exhibits any crystallinity, it preferably has a % crystallinity of 0.1% to 5%, preferably 0.1% to 3%. (Crystallinity is determined by dividing (i) the measured heat of fusion by (ii) the heat of fusion of 100% crystalline polyethylene, which has a value of 293 J / g (B. Wunderlich, Thermal Analysis, Academic Press, 1990, pp. 417-431)).
[0093] The stereoregularity of α-olefin-ethylene-diene polymers is determined by 13 C NMR measurement. The polypropylene microstructure is measured by 13 The C-NMR spectrum measures, among other things, the concentrations of isotactic and syndiotactic diads ([m] and [r]), triads ([mm] and [rr]), and pentads ([mmmm] and [rrrr]). The designation "m" or "r" describes the stereochemistry of adjacent propylene pairs, "m" referring to meso and "r" to racemic. The polymer resonance peak is referenced to mmmm = 21.8 ppm. The calculations involved in characterizing polymers by NMR are described by FA Bovey in Polymer Conformation and Configuration (Academic Press, New York 1969) and by J. Randall in Polymer Sequence Determination, 13 C-NMR Method (Academic Press, New York, 1977).
[0094] The "propylene stereoregularity index" (expressed herein as [m / r]) is calculated as defined in HN Cheng, Macromolecules, 17, p. 1950 (1984). When [m / r] is 0 to less than 1.0, the polymer is generally described as syndiotactic, when [m / r] is 1.0, the polymer is atactic, and when [m / r] is greater than 1.0, the polymer is generally described as isotactic. The [m / r] region from 0-1.0 is a continuous region, where polymers with values closer to zero are more syndiotactic and those with values closer to one are more atactic. The phrases "propylene stereoregularity index," "stereoregularity index," and "C 3+ The terms "olefin stereoregularity index" and "olefin stereoregularity index" are used interchangeably.
[0095] For polypropylene, the "mm triad tacticity index" of a polymer is a measure of the relative isotacticity of a sequence of three adjacent propylene units linked in a head-to-tail configuration. More specifically, in the present invention, the mm triad tacticity index (also called the "mm fraction") of a polypropylene homopolymer or copolymer is expressed as the ratio of the number of units of meso tacticity to the number of all propylene triads in the copolymer:
[0096]
[0097] Wherein PPP(mm), PPP(mr) and PPP(rr) represent the peak areas of the methyl group of the second unit in the possible triad configuration of three head-to-tail propylene units as shown in the Fischer projection schematic below:
[0098]
[0099] The "rr triad tacticity index" of a polymer is a measure of the relative syndiotactic tacticity of a sequence of three adjacent propylene units linked in a head-to-tail configuration. More specifically, in the present invention, the rr triad tacticity index (also referred to as the "rr score") of a polypropylene homopolymer or copolymer is expressed as the ratio of the number of units of racemic tacticity to the number of all propylene triads in the copolymer:
[0100]
[0101] Calculation of the mm fraction of propylene polymers is described in U.S. Pat. No. 5,504,172 (homopolymers: column 25, line 49 to column 27, line 26; copolymers: column 28, line 38 to column 29, line 67). For more information on how the mm triad tacticity can be determined from the 13C NMR spectrum, see 1) JA Wen, Catalytic Polymerization of Olefins: Proceedings of the International Sympos ium on Future Aspects of Olefin Polymerization, T. Keii and K. Soga, Eds. (Elsevier, 1986), pp. 271-292; and 2) U.S. Patent Application Publication No. US 2004 / 054086 (to paragraph).
[0102] Similarly, m dyads and r dyads can be calculated as follows, where mm, mr and mr are as defined above:
[0103] m=mm+ 1 / 2mr
[0104] r=rr+ 1 / 2mr.
[0105] Preferably, the α-olefin-ethylene-diene polymer of the present disclosure has a "propylene stereoregularity index" [m / r] greater than 0.30, or greater than 0.40, or greater than 0.50, and has an upper limit of 1.2, or 1.1, or 1.0, or 0.9.
[0106] Can be used for other C 3+ Similar calculations are performed for olefin polymers (including those with low ethylene content). For further information, see JC Randall, Polymer Reviews, "A review of high resolution liquid 13 C NMR characterizations of ethylene-based polymers" (1989) 29:2201-317.
[0107] Additionally, as described above, when a sample shows no melting peaks, as in the case of amorphous polymers, it can be said to have no Hf. However, for example, even some amorphous or nearly amorphous PEDM samples may show minor melting peaks, such that the Hf on the first melt may be observed to be <1 J / g. Therefore, for the purposes of this application, a PEDM may be considered amorphous when it has a Hf <1 J / g, or when it does not exhibit a discernible melting peak. For example, the PEDM terpolymer described herein may have an Hf of <1 J / g, which is measured by the DSC procedure described herein from the first heating cycle after, for example, annealing at 140°C for 5 minutes and then aging at room temperature for 1 hour, or 1 day, or 1 week, or 4 weeks, or 3 months.
[0108] The PEDM terpolymers of some embodiments may have a Tg of -45°C to -2°C, or -40°C to -25°C, -40°C to -20°C, -35°C to -25°C, -40°C to -15°C, or -35°C to -15°C; or -20°C to -2°C, or -15°C to -2°C, or -10°C to -2°C, or -5°C to -2°C, as determined by the DSC procedure described herein.
[0109] The PEDM terpolymers of the present disclosure may have a Tg (°C) greater than or equal to -7.386-(87.98×E)+(294×D) and less than or equal to -1.386-(87.98×E)+(294×D), where E is the mole fraction of ethylene in the polymer and D is the mole fraction of diene in the polymer. The PEDM terpolymers of the present disclosure may have a Tg (°C) greater than or equal to -6.886-(87.98×E)+(294×D) and less than or equal to -1.886-(87.98×E)+(294×D), where E is the mole fraction of ethylene in the polymer and D is the mole fraction of diene in the polymer.
[0110] PEDM terpolymers can be prepared by a polymerization process comprising contacting propylene, C2, C4-12 alpha-olefins (e.g., ethylene), and a diene (e.g., ENB) with a catalyst system comprising an activator, an optional support, and a catalyst compound. The catalyst compound, optional support, and activator can be combined in any order, and are typically combined prior to contacting the catalyst system with the monomers.
[0111] The polymerization process of the present disclosure can be carried out in any suitable manner, such as any suitable suspension, homogeneous, bulk, solution, slurry or gas phase polymerization process. These processes can be operated in batch, semi-batch or continuous mode. Gas phase polymerization processes and slurry processes are preferred. Additional descriptions of methods for preparing PEDM terpolymers are described in PCT / US2019 / 022738 filed on March 18, 2019 and PCT / US2019 / 022764 filed on March 18, 2019, both of which are incorporated herein by reference in their entirety.
[0112] The present disclosure provides a polymerization process wherein propylene, C2, C4-C 12 Olefins (such as ethylene) and dienes (such as ENB) are contacted with a catalyst system comprising an activator, an optional support, and a catalyst compound. The catalyst compound, optional support, and activator may be combined in any order, and are typically combined before contacting the catalyst system with the monomer. In at least one embodiment, the catalyst compound is represented by the following formula (I):
[0113] T y Cp' m MG n X q (I)
[0114] in:
[0115] Cp' is an optionally substituted or unsubstituted tetrahydroindacenyl (e.g., tetrahydro-s-indacenyl or tetrahydro-as-indacenyl), provided that when Cp' is tetrahydro-s-indacenyl: 1) the 3 and / or 4 positions are not aryl or substituted aryl, 2) the 3 position is not directly bonded to a Group 15 or 16 heteroatom, 3) there are no additional rings fused to the tetrahydroindacenyl ligand, 4) T is not bonded to the 2 position, and 5) the 5, 6 or 7 positions (preferably the 6 position) are geminally disubstituted, preferably by two C1-C 10 Alkyl geminal disubstituted;
[0116] M is a Group 2, 3, 4, 5 or 6 transition metal, preferably a Group 4 transition metal, such as titanium, zirconium or hafnium (preferably titanium);
[0117] T is a bridging group (eg, dialkylsilylene, dialkylcarbylene, benzene-1,2-diyl, substituted benzene-1,2-diyl, cyclohexane-1,2-diyl or substituted cyclohexane-1,2-diyl). T is preferably (CR 8 R 9 ) x 、SiR 8 R 9 or GeR8 R 9 , where x is 1 or 2, R 8 and R 9 R is independently selected from hydrogen, substituted or unsubstituted hydrocarbon, halogenated hydrocarbon, silyl hydrocarbon and germyl hydrocarbon, 8 and R 9 may be optionally bonded together to form a ring structure. In a particular embodiment, R 8 and R 9 is not aromatic);
[0118] y is 0 or 1, indicating the absence or presence of T;
[0119] G is composed of the formula JR i z-y A heteroatom group represented by wherein J is N, P, O or S, R i It is C1-C 100 Hydrocarbon (e.g. C1-C 20 alkyl), and when J is N or P, z is 2, and when J is O or S, z is 1 (preferably, J is N and z is 2) (R i Can be linear, branched or cyclic C1-C 20 Hydrocarbyl, preferably independently selected from methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, phenyl and isomers thereof, including tert-butyl, cyclododecyl, cyclooctyl, preferably tert-butyl and / or cyclododecyl);
[0120] X is a leaving group (e.g., a halide, a hydride, an alkyl group, an alkenyl group, or an aralkyl group), and optionally, two or more X groups may form part of a fused ring or ring system;
[0121] m=1; n=1, 2 or 3; q=1, 2 or 3; and the sum of m+n+q is equal to the oxidation state of the transition metal (preferably 3, 4, 5 or 6, preferably 4); preferably m=1, n=1, q is 2, y=1.
[0122] In at least one embodiment of formula (I), M is a Group 4 transition metal (preferably Hf, Ti and / or Zr, preferably Ti). In at least one embodiment of formula (I), JR i z-y is cyclododecylamino, tert-butylamino and / or 1-adamantylamino.
[0123] In at least one embodiment of formula (I), each X is independently selected from a hydrocarbon group containing 1 to 20 carbon atoms, an aryl group, a hydride, an amide, an alkoxide, a sulfide, a phosphide, a halide, a diene, an amine, a phosphine, an ether, and combinations thereof, (two Xs may form part of a fused ring or ring system), preferably, each X is independently selected from a halide, an aryl group, and a C1-C5 alkyl group, preferably, each X is a benzyl, methyl, ethyl, propyl, butyl, pentyl, or chloro group.
[0124] In at least one embodiment of formula (I), the Cp' group may be substituted with a combination of substituents R. R includes one or more of the following groups: hydrogen, or a linear, branched alkyl, or an alkenyl, alkynyl, cycloalkyl or aryl, acyl, alkoxy, aryloxy, alkylthio, dialkylamino, alkoxycarbonyl, aryloxycarbonyl, carbamoyl, alkyl- or dialkylcarbamoyl, acyloxy, acylamino, arylamino, linear, branched or cyclic alkylene, or a combination thereof. In at least one embodiment, the substituent R has up to 50 non-hydrogen atoms, preferably 1-30 carbon atoms, which may also be substituted by halogens or heteroatoms, etc., provided that when Cp' is tetrahydro-s-indacenyl: 1) the 3 and / or 4 positions are not aryl or substituted aryl, 2) the 3-position is not substituted by a Group 15 or 16 heteroatom, 3) there are no additional rings fused to the tetrahydroindacenyl ligand, T is not bonded to the 2-position, 5) the 5, 6 or 7-position (preferably the 6-position) is geminally disubstituted, preferably by two C1-C 10 Alkyl geminal disubstituted. Non-limiting examples of alkyl substituents R include methyl, ethyl, propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl, benzyl or phenyl, including all isomers thereof, such as tert-butyl, isopropyl, etc. Other hydrocarbon groups include fluoromethyl, fluoroethyl, difluoroethyl, iodopropyl, bromohexyl, chlorobenzyl and hydrocarbon-substituted organometalloid groups, including trimethylsilyl, trimethylgermyl, methyldiethylsilyl, etc.; and halogenated hydrocarbon-substituted organometalloid groups, including tris(trifluoromethyl)-silyl, methyl-bis(difluoromethyl)silyl, bromomethyldimethylgermyl, etc.; and disubstituted boron groups, including, for example, dimethyl boron; disubstituted nitrogen group groups, including dimethylamine, dimethylphosphine, diphenylamine, methylphenylphosphine; chalcogen group groups, including methoxy, ethoxy, propoxy, phenoxy, dimethyl sulfide and diethyl sulfide. Non-hydrogen substituents R include atoms carbon, silicon, boron, aluminum, nitrogen, phosphorus, oxygen, tin, sulfur, germanium, and the like, including olefins, such as, but not limited to, olefinically unsaturated substituents, including vinyl terminated ligands, such as but-3-enyl, prop-2-enyl, hex-5-enyl, and the like.
[0125] In at least one embodiment of formula (I), the substituent(s) R are independently a hydrocarbon group, a heteroatom or a heteroatom-containing group, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl or isomers thereof, or a C1-C1-C2-substituted heteroatom having N, O, S and / or P. 20 a hydrocarbon group or a heteroatom-containing group (typically containing up to 12 atoms, including N, O, S and P heteroatoms), provided that when Cp' is tetrahydro-s-indacenyl, the 3 and / or 4 positions are not aryl or substituted aryl, the 3 position is not substituted with a Group 15 or 16 heteroatom, there are no additional rings fused to the tetrahydroindacenyl ligand, T is not bonded to the 2-position, and the 5, 6 or 7-positions (preferably the 6-position) are geminally disubstituted, preferably with two C1-C 10 alkyl.
[0126] In at least one embodiment of formula (I), the Cp' group is tetrahydro-as-indacenyl or tetrahydro-s-indacenyl which may be substituted.
[0127] When T is a bridging group containing at least one element of Group 13, 14, 15 or 16, especially boron or an element of Group 14, 15 or 16, y may be 1. Examples of suitable bridging groups include P(=S)R*, P(=Se)R*, P(=O)R*, R*2C, R*2Si, R*2Ge, R*2CCR*2, R*2CCR*2CR*2, R*2CCR*2CR*2CR*2, R*C=CR*, R*C=CR*CR*2, R*2CCR*=CR*CR*2, R*C=CR*CR*=CR*, R*C=CR*CR*2CR*2, R*2CSiR*2, R*2SiSiR*2, R*2 SiOSiR*2, R*2CSiR*2CR*2, R*2SiCR*2SiR*2, R*C=CR*SiR*2, R*2CGeR*2, R*2GeGeR*2, R*2CGeR*2CR*2, R*2Ge CR*2GeR*2, R*2SiGeR*2, R*C=CR*GeR*2, R*B, R*2C-BR*, R*2C-BR*-CR*2, R*2C-O-CR*2, R*2CR*2C-O-CR*2CR*2 , R*2C-O-CR*2CR*2, R*2C-O-CR*=CR*, R*2C-S-CR*2, R*2CR*2C-S-CR*2CR*2, R*2C-S-CR*2CR*2, R*2C-S-CR*= CR*, R*2C-Se-CR*2, R*2CR*2C-Se-CR*2CR*2, R*2C-Se-CR*2CR*2, R*2C-Se-CR*=CR*, R*2C-N=CR*, R*2C-NR*-C R*2, R*2C-NR*-CR*2CR*2, R*2C-NR*-CR*=CR*, R*2CR*2C-NR*-CR*2CR*2, R*2C-P=CR*, R*2C-PR*-CR*2, O, S, Se, Te, NR*, PR*, AsR*, SbR*, OO, SS, R*N-NR*, R*P-PR*, OS, O-NR*, O-PR*, S-NR*, S-PR* and R*N-PR*, wherein R* is hydrogen or a C1-C 20 The substituents are alkyl, substituted alkyl, halogenated alkyl, substituted halogenated alkyl, silylalkyl or germylalkyl. Optionally, two or more adjacent R* may be joined to form a substituted or unsubstituted, saturated, partially unsaturated or aromatic, cyclic or polycyclic substituent. Optionally, any one or more adjacent R* and R iCan be joined to form substituted or unsubstituted, saturated, partially unsaturated or aromatic, cyclic or polycyclic substituents. Preferred examples of bridging group T include -CH2-, -CH2CH2-, -SiMe2-, -SiPh2-, -Si(Me)(Ph)-, -Si(CH2)3-, -Si(CH2)4-, -O-, -S-, -N(Ph)-, -P(Ph)-, -N(Me)-, -P(Me)-, -N(Et)-, -N(Pr)-, -N(Bu)-, -P(Et)-, -P(Pr)-, -(Me)2SiOSi(Me)2- and -P(Bu)-. In a preferred embodiment of the present disclosure, when Cp' is tetrahydro-s-indacene and T is R*2Si, then R* is not aryl. In some embodiments, R* is not aryl or substituted aryl.
[0128] In at least one embodiment, the catalyst compound is one or more bridged transition metal compounds represented by the following formula (II):
[0129]
[0130] wherein M is a Group 4 metal (e.g., Hf, Ti or Zr, preferably Ti);
[0131] J is N, O, S or P;
[0132] When J is N or P, p is 2, and when J is O or S, p is 1 (preferably J is N, y=1, p=2);
[0133] Each R a Independently C1-C 10 Alkyl (or C2-C 10 alkyl);
[0134] Each R b and each R c are independently hydrogen or C1-C 10 Alkyl (or C2-C 10 alkyl);
[0135] Each R 2 , R 3 , R 4 and R 7 are independently hydrogen, or C1-C 50 Substituted or unsubstituted hydrocarbon, halogenated hydrocarbon, silyl hydrocarbon or germyl hydrocarbon, provided that: 1) R 3 and / or R 4 is not an aryl group or a substituted aryl group, 2) R 3 is not directly bonded to a Group 15 or 16 heteroatom, and 3) an adjacent R 4 , Rc , R a , R b or R 7 They do not join together to form a fused ring system;
[0136] Each R' is independently C1-C 100 a substituted or unsubstituted hydrocarbon group, a halogenated hydrocarbon group, a silyl hydrocarbon group or a germyl hydrocarbon group;
[0137] T is a bridging group, and y is 0 or 1, indicating that T is absent (y=0) or present (y=1);
[0138] Each X is independently a leaving group, or two X are joined and bonded to a metal atom to form a metal cyclize ring, or two X are joined to form a chelate ligand, a diene ligand or an alkylidene group.
[0139] In at least one embodiment, the catalyst compound is one or more bridged transition metal compounds represented by the following formula (III):
[0140]
[0141] wherein M is a Group 4 metal (e.g., Hf, Ti or Zr, preferably Ti);
[0142] J is N, O, S or P;
[0143] When J is N or P, p is 2, and when J is O or S, p is 1 (preferably J is N, y=1, p=2);
[0144] Each R d , R e and R f are independently hydrogen or C1-C 10 Alkyl (or C2-C 10 alkyl);
[0145] Each R 2 , R 3 , R 6 and R 7 are independently hydrogen, or C1-C 50 a substituted or unsubstituted hydrocarbon group, a halogenated hydrocarbon group, a silyl hydrocarbon group or a germyl hydrocarbon group;
[0146] Each R' is independently C1-C 100 a substituted or unsubstituted hydrocarbon group, a halogenated hydrocarbon group, a silyl hydrocarbon group or a germyl hydrocarbon group;
[0147] T is a bridging group, and y is 0 or 1, indicating that T is absent (y=0) or present (y=1);
[0148] Each X is independently a leaving group, or two X are joined and bonded to a metal atom to form a metal cyclize ring, or two X are joined to form a chelate ligand, a diene ligand or an alkylidene group.
[0149] In some embodiments of Formula II and III, y is 1 and T is (CR 8 R 9 ) x 、SiR 8 R 9 or GeR 8 R 9 , where x is 1 or 2, R 8 and R 9 R is independently selected from hydrogen or substituted or unsubstituted hydrocarbon, halogenated hydrocarbon, silyl hydrocarbon and germyl hydrocarbon. 8 and R 9 They may optionally be bonded together to form a ring structure.
[0150] In at least one embodiment of the present disclosure, each R 2 , R 3 , R 6 and R 7 are independently hydrogen, or C1-C 50 The substituted or unsubstituted hydrocarbon group, halogenated hydrocarbon group, silyl hydrocarbon group or germyl hydrocarbon group is preferably methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl and dodecyl or isomers thereof.
[0151] In at least one embodiment of the present disclosure, each R 2 , R 3 , R 4 and R 7 are independently hydrogen, or C1-C 50 The substituted or unsubstituted hydrocarbon group, halogenated hydrocarbon group, silyl hydrocarbon group or germyl hydrocarbon group is preferably methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl and dodecyl or isomers thereof.
[0152] In at least one embodiment of the present disclosure, each R a or R d Independently selected from methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl and isomers thereof, preferably methyl and ethyl, preferably methyl.
[0153] In at least one embodiment of the present disclosure, each R b , R c , R e or R fIndependently selected from hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl and isomers thereof, preferably hydrogen or methyl, preferably hydrogen.
[0154] In at least one embodiment of the present disclosure, each R a independently selected from methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl and isomers thereof, preferably methyl and ethyl, preferably methyl, each R b and R c Independently selected from hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl and isomers thereof, preferably hydrogen or methyl, preferably hydrogen.
[0155] In at least one embodiment of the present disclosure, each R d independently selected from hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl and isomers thereof, preferably methyl and ethyl, preferably methyl, each R e and R f Independently selected from hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl and isomers thereof, preferably hydrogen or methyl, preferably hydrogen.
[0156] In at least one embodiment of the present disclosure, each R a , R b and R c Independently selected from hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl and isomers thereof, preferably hydrogen or methyl.
[0157] In at least one embodiment of the present disclosure, each R d , R e and R f Independently selected from hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl and isomers thereof, preferably hydrogen or methyl.
[0158] In at least one embodiment of the present disclosure, R' is C1-C 100 Substituted or unsubstituted hydrocarbon, halogenated hydrocarbon or silyl hydrocarbon, preferably methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, phenyl or isomers thereof, preferably tert-butyl, neopentyl, cyclohexyl, cyclooctyl, cyclododecyl, adamantyl or norbornyl.
[0159] In at least one embodiment of the present disclosure, T is CR 8 R 9 , R 8 R9 C-CR 8 R 9 、SiR 8 R 9 or GeR 8 R 9 , where R 8 and R 9 R is independently selected from hydrogen or substituted or unsubstituted hydrocarbon, halogenated hydrocarbon, silyl hydrocarbon, 8 and R 9 may be optionally bonded together to form a ring structure, preferably each R 8 and R 9 R is independently methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, benzyl, phenyl, methylphenyl or an isomer thereof, preferably methyl, ethyl, propyl, butyl or hexyl. 8 and R 9 When optionally bonded together, preferred bridges include substituted or unsubstituted benzene-1,2-diyl, cyclohexane-1,2-diyl, cyclopentamethylenesilylene, cyclotetramethylenesilylene, cyclotrimethylenesilylene and dibenzo[b,d]methoxysilyl. In addition, optionally, any one or more adjacent R 8 and / or R 9 Substituents which together with R' may form a substituted or unsubstituted, saturated, partially unsaturated or aromatic, cyclic or polycyclic substituent.
[0160] In at least one embodiment of the present disclosure, R 8 or R 9 In at least one embodiment of the present disclosure, R 8 is not an aryl group. In at least one embodiment of the present disclosure, R 9 is not an aryl group. In at least one embodiment of the present disclosure, R 8 and R 9 Not aromatic.
[0161] In at least one embodiment of the present disclosure, R 8 and R 9 Independently C1-C 10 Alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl or isomers thereof.
[0162] In at least one embodiment of the present disclosure, each R 2 , R 3 , R 4 and R 7 are independently hydrogen or a hydrocarbon group. 2 , R3 , R 4 and R 7 can be independently hydrogen or C1-C 10 Alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl or isomers thereof.
[0163] In at least one embodiment of the present disclosure, each R 2 , R 3 , R 6 and R 7 are independently hydrogen or a hydrocarbon group. 2 , R 3 , R 6 and R 7 can be independently hydrogen or C1-C 10 The alkyl group is preferably a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group or an isomer thereof.
[0164] In at least one embodiment of the present disclosure, R 2 It is C1-C 10 Alkyl, R 3 , R 4 and R 7 It's hydrogen.
[0165] In at least one embodiment of the present disclosure, R 2 It is C1-C 10 Alkyl, R 3 , R 6 and R 7 It's hydrogen.
[0166] In at least one embodiment of the present disclosure, R 2 , R 3 , R 4 and R 7 is hydrogen. In at least one embodiment of the present disclosure, R 2、 R 3 , R 6 and R 7 It's hydrogen.
[0167] In at least one embodiment of the present disclosure, R 2 is methyl, ethyl, or an isomer of propyl, butyl, pentyl or hexyl, R 3 , R 4 and R 7 is hydrogen. In at least one embodiment of the present disclosure, R 2 is methyl, ethyl, or an isomer of propyl, butyl, pentyl or hexyl, R 3 , R 6 and R7 It's hydrogen.
[0168] In at least one embodiment of the present disclosure, R 2 is methyl, R 3 , R 4 and R 7 is hydrogen. In at least one embodiment of the present disclosure, R 2 is methyl, R 3 , R 6 and R 7 It's hydrogen.
[0169] In at least one embodiment of the present disclosure, R 3 is hydrogen. In at least one embodiment of the present disclosure, R 2 It's hydrogen.
[0170] In at least one embodiment of the present disclosure, R 2 and each R a Independently C1-C 10 Alkyl, R 3 , R 4 , R 7 and each R b and R c It's hydrogen.
[0171] In at least one embodiment of the present disclosure, R 2 and each R d Independently C1-C 10 Alkyl, R 3 , R 6 , R 7 and each R e and R f It's hydrogen.
[0172] In at least one embodiment of the present disclosure, R 2 and each R a are independently methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl or isomers thereof, R 3 , R 4 , R 7 and each R b and R c It's hydrogen.
[0173] In at least one embodiment of the present disclosure, R 2 and each R d are independently methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl or isomers thereof, R 3 , R 6 , R7 and each R e and R f It's hydrogen.
[0174] In at least one embodiment of the present disclosure, R' is C1-C 100 or C1-C 30 Substituted or unsubstituted hydrocarbon group.
[0175] In at least one embodiment of the present disclosure, R' is C1-C 30 Substituted or unsubstituted alkyl (linear, branched or cyclic), aryl, alkaryl or heterocyclic group. In at least one embodiment of the present disclosure, R' is C1-C 30 Linear, branched or cyclic alkyl groups.
[0176] In at least one embodiment of the present disclosure, R' is methyl, ethyl, or any isomer of propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl or dodecyl. In at least one embodiment of the present disclosure, R' is a cyclic or polycyclic hydrocarbon group.
[0177] In at least one embodiment of the present disclosure, R' is selected from tert-butyl, neopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, cycloundecyl, cyclododecyl, adamantyl, and norbornyl. In at least one embodiment, R' is tert-butyl.
[0178] In at least one embodiment of the present disclosure, R i is selected from the group consisting of tert-butyl, neopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, cycloundecyl, cyclododecyl, adamantyl and norbornyl. In at least one embodiment, R i It is tert-butyl.
[0179] In at least one embodiment of the present disclosure, T is selected from diphenylmethylene, dimethylmethylene, 1,2-ethylene, benzene-1,2-diyl, cyclohexane-1,2-diyl, cyclotrimethylenesilylene, cyclotetramethylenesilylene, cyclopentamethylenesilylene, dibenzo[b,d]methoxysilyl, dimethylsilylene, diethylsilylene, methylethylsilylene, and dipropylsilylene.
[0180] In at least one embodiment of the present disclosure, each R a R is independently methyl, ethyl, propyl, butyl, pentyl or hexyl. In at least one embodiment of the present disclosure, each R a is independently methyl or ethyl. a It may be methyl.
[0181] In at least one embodiment of the present disclosure, each R d R is independently methyl, ethyl, propyl, butyl, pentyl or hexyl. In at least one embodiment of the present disclosure, each R d is independently methyl or ethyl. d It may be methyl.
[0182] In at least one embodiment of the present disclosure, each R d and each R e and R f R is independently hydrogen, methyl, ethyl, propyl, butyl, pentyl or hexyl. In at least one embodiment of the present disclosure, each R d is independently hydrogen, methyl or ethyl.
[0183] In at least one embodiment of the present disclosure, each R b and R c is hydrogen. In at least one embodiment of the present disclosure, each R e and R f It's hydrogen.
[0184] In at least one embodiment of the present disclosure, each X is a hydrocarbyl, a halohydrocarbyl, or a substituted hydrocarbyl or halohydrocarbyl.
[0185] In at least one embodiment of the present disclosure, X is methyl, benzyl, or halide, wherein halide includes fluoro, chloro, bromo, and iodo.
[0186] In at least one embodiment of the present disclosure, two X are joined together to form C4-C 20 Examples of the diene ligand include 1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, and 2,4-dimethylpentadiene.
[0187] In at least one embodiment of Formula (II) of the present disclosure: 1) R 3 and / or R 4 is not an aryl group or a substituted aryl group, 2) R 3 is not directly bonded to a Group 15 or 16 heteroatom, and 3) an adjacent R 4 , R c , R a , R b or R 7 are not joined together to form a fused ring system, and 4) each R a It is C1-C 10 Alkyl (preferably methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl or isomers thereof).
[0188] In a preferred embodiment of the present disclosure, T in any of formulas (I)-(III) is represented by the formula ER g 2 or (ER g 2)2 represents, where E is C, Si or Ge, each R g are independently hydrogen, halogen, C1 to C 20 A hydrocarbon group (e.g., methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl or dodecyl) or a C1 to C 20 Substituted hydrocarbon, two R g A cyclic structure including an aromatic, partially saturated or saturated cyclic or condensed ring system can be formed. Preferably, T is a bridging group comprising carbon or silicon dioxide, such as a dialkylsilyl group, preferably, T is selected from -CH2-, -CH2CH2-, -C(CH3)2-, Si(Me)2, cyclotrimethylenesilylene (-Si(CH2)3-), cyclopentamethylenesilylene (-Si(CH2)5-) and cyclotetramethylenesilylene (-Si(CH2)4-).
[0189] In at least one embodiment, the catalyst compound is one or more of the following:
[0190] Dimethylsilylene (2,6,6-trimethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(tert-butylamino) M (R) 2;
[0191] Dimethylsilylene (6,6-dimethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(tert-butylamino) M (R) 2;
[0192] Dimethylsilylene (2,7,7-trimethyl-3,6,7,8-tetrahydro-as-indacen-3-yl) (tert-butylamino) M (R) 2;
[0193] Dimethylsilylene (7,7-dimethyl-3,6,7,8-tetrahydro-as-indacen-3-yl)(tert-butylamino) M (R) 2;
[0194] Dimethylsilylene (2,6,6-trimethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(cyclododecylamino) M (R) 2;
[0195] Dimethylsilylene (6,6-dimethyl-1,5,6,7-tetrahydro-s-indacene-1-yl)(cyclododecylamino) M (R) 2;
[0196] Dimethylsilylene (2,7,7-trimethyl-3,6,7,8-tetrahydro-as-indacene-3-yl) (cyclododecylamino) M (R) 2;
[0197] Dimethylsilylene (7,7-dimethyl-3,6,7,8-tetrahydro-as-indacene-3-yl) (cyclododecylamino) M (R) 2;
[0198] Dimethylsilylene (2,6,6-trimethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(cyclohexylamino) M (R) 2;
[0199] Dimethylsilylene (6,6-dimethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(cyclohexylamino) M (R) 2;
[0200] Dimethylsilylene (2,7,7-trimethyl-3,6,7,8-tetrahydro-as-indacen-3-yl)(cyclohexylamino) M (R) 2;
[0201] Dimethylsilylene (7,7-dimethyl-3,6,7,8-tetrahydro-as-indacen-3-yl)(cyclohexylamino) M (R) 2;
[0202] Dimethylsilylene (2,6,6-trimethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(adamantylamino) M (R) 2;
[0203] Dimethylsilylene (6,6-dimethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(adamantylamino) M (R) 2;
[0204] Dimethylsilylene (2,7,7-trimethyl-3,6,7,8-tetrahydro-as-indacen-3-yl)(adamantylamino) M (R) 2;
[0205] Dimethylsilylene (7,7-dimethyl-3,6,7,8-tetrahydro-as-indacene-3-yl)(adamantylamino) M (R) 2;
[0206] Dimethylsilylene (2,6,6-trimethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(neopentylamino) M (R) 2;
[0207] Dimethylsilylene (6,6-dimethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(neopentylamino) M (R) 2;
[0208] Dimethylsilylene (2,7,7-trimethyl-3,6,7,8-tetrahydro-as-indacen-3-yl)(neopentylamino) M (R) 2;
[0209] Dimethylsilylene (7,7-dimethyl-3,6,7,8-tetrahydro-as-indacene-3-yl)(neopentylamino) M (R) 2;
[0210] Dimethylsilylene (2-methyl-6,6-diethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(tert-butylamino) M (R) 2;
[0211] Dimethylsilylene (6,6-diethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(tert-butylamino) M (R) 2;
[0212] Dimethylsilylene (2-methyl-7,7-diethyl-3,6,7,8-tetrahydro-as-indacen-3-yl) (tert-butylamino) M (R) 2;
[0213] Dimethylsilylene (7,7-diethyl-3,6,7,8-tetrahydro-as-indacen-3-yl)(tert-butylamino) M (R) 2;
[0214] Dimethylsilylene (2-methyl-6,6-diethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(cyclododecylamino) M (R) 2;
[0215] Dimethylsilylene (6,6-diethyl-1,5,6,7-tetrahydro-s-indacene-1-yl)(cyclododecylamino) M (R) 2;
[0216] Dimethylsilylene (2-methyl-7,7-diethyl-3,6,7,8-tetrahydro-as-indacene-3-yl) (cyclododecylamino) M (R) 2;
[0217] Dimethylsilylene (7,7-dimethyl-3,6,7,8-tetrahydro-as-indacene-3-yl) (cyclododecylamino) M (R) 2;
[0218] Diethylsilylene (2,6,6-trimethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(tert-butylamino) M (R) 2;
[0219] Diethylsilylene (6,6-dimethyl-1,5,6,7-tetrahydro-s-indacen-1-yl)(tert-butylamino) M (R) 2;
[0220] Diethylsilylene (2,7,7-trimethyl-3,6,7,8-tetrahydro-as-indacen-3-yl) (tert-butylamino) M (R) 2;
[0221] Diethylsilylene (7,7-dimethyl-3,6,7,8-tetrahydro-as-indacen-3-yl)(tert-butylamino) M (R) 2;
[0222] Dimethylsilylene (2-methyl-3,6,7,8-tetrahydro-as-indacen-3-yl)(cyclohexylamino) M (R) 2;
[0223] Dimethylsilylene (2-methyl-3,6,7,8-tetrahydro-as-indacene-3-yl)(cyclododecylamino) M (R) 2;
[0224] Dimethylsilylene (2-methyl-3,6,7,8-tetrahydro-as-indacen-3-yl)(adamantylamino) M (R) 2; and
[0225] Dimethylsilylene (2-methyl-3,6,7,8-tetrahydro-as-indacen-3-yl) (tert-butylamino) M (R) 2,
[0226] Wherein M is selected from Ti, Zr and Hf, R is selected from halogen or C1-C5 alkyl, preferably R is methyl or halogen, and preferably M is Ti.
[0227] In alternative embodiments, the catalyst system can include two or more different transition metal compounds. For the present disclosure, if a transition metal compound differs from another at least one atom, then it is considered that they are different. For example, "Me2Si(2,7,7-Me3-3,6,7,8-tetrahydro-as-indacene-3-yl) (cyclohexylamino) TiCl2" is different from Me2Si(2,7,7-Me3-3,6,7,8-tetrahydro-as-indacene-3-yl) (n-butylamido) TiCl2", which is different from Me2Si(2,7,7-Me3-3,6,7,8-tetrahydro-as-indacene-3-yl) (butylamido) HfCl2.
[0228] In some embodiments, Formulas I through III are referred to as mono-tetrahydroindacene-based compounds, procatalysts, and / or catalysts.
[0229] In at least one embodiment, a mono-tetrahydroindacene-based compound as described herein is used in the catalyst system.
[0230] Activator
[0231] The terms "cocatalyst" and "activator" are used interchangeably herein and include compounds capable of activating any of the above catalyst compounds by converting the neutral catalyst compound into a catalytically active catalyst compound cation. Non-limiting examples of activators include aluminoxanes, aluminum alkyls, ionizing activators (which may be neutral or ionic), and conventional types of cocatalysts. Preferred activators typically include non-coordinating anion compounds, aluminoxane compounds, modified aluminoxane compounds, and ionizing anion precursor compounds that extract reactive, sigma-bonded metal ligands, thereby cationizing the metal complex and providing a charge-balancing non-coordinating or weakly coordinating anion.
[0232] Aluminoxane Activator
[0233] Aluminoxane activators are used as activators in the catalyst systems described herein. Aluminoxanes are generally 1 )-O-subunit oligomer compound, wherein R 1 It is an alkyl group. Examples of aluminoxanes include methylaluminoxane (MAO), modified methylaluminoxane (MMAO), ethylaluminoxane and isobutylaluminoxane. Alkylaluminoxanes and modified alkylaluminoxanes are suitable as catalyst activators, especially when the extractable ligand is an alkyl, halide, alkoxy or amino group. Mixtures of different aluminoxanes and modified aluminoxanes can also be used. Visually transparent methylaluminoxane can be preferably used. Turbid or gel aluminoxane can be filtered to prepare a clear solution or a transparent aluminoxane can be decanted from the turbid solution. Useful aluminoxanes are modified methylaluminoxane (MMAO) cocatalyst 3A type (commercially available from Akzo Chemicals, Inc. under the trade name modified methylaluminoxane 3A type) covered by U.S. Patent No. US5,041,584.
[0234] When the activator is an aluminoxane (modified or unmodified), some embodiments select a maximum activator amount typically at up to 5000-fold molar excess (Al / M) relative to the catalyst compound (per metal catalytic site). The minimum activator to catalyst compound is a 1:1 molar ratio. Alternative preferred ranges include 1:1-500:1, or 1:1-200:1, or 1:1-100:1, or 1:1-50:1.
[0235] Non-coordinating anion activators
[0236] Non-coordinating anion activators may also be used herein. The term "non-coordinating anion" (NCA) refers to an anion that is not coordinated to the cation or is only weakly coordinated to the cation, thereby remaining sufficiently unstable to be replaced by a neutral Lewis base. "Compatible" non-coordinating anions are those that do not degrade to neutrality when the initially formed complex decomposes. In addition, the anion does not transfer anionic substituents or fragments to the cation, causing it to form a neutral transition metal compound and neutral byproducts from the anion. Non-coordinating anions that can be used in accordance with the present disclosure are anions that are compatible, stabilizing the transition metal cation at +1 in the sense of balancing its ionic charge, yet remaining sufficiently unstable to allow displacement during the polymerization process.
[0237] It is within the scope of the present disclosure to use neutral or ionic ionizing activators, such as tri(n-butyl)ammonium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N-dimethylanilinium tetrakis(perfluoronaphthyl)borate, triperfluorophenylboronylmetalloid precursor or triperfluoronaphthylboronylmetalloid precursor, polyhalogenated heteroborane anions (WO 98 / 43983), boric acid (U.S. Pat. No. 5,942,459), alone or in combination with the aluminoxane or modified aluminoxane activators. It is also within the scope of the present disclosure to use neutral or ionic activators in combination with the aluminoxane or modified aluminoxane activators.
[0238] The catalyst system of the present disclosure may include at least one non-coordinating anion (NCA) activator. In particular, the catalyst system may include an NCA that does not coordinate to a cation or only weakly coordinates to a cation, thereby remaining sufficiently labile to be displaced during polymerization.
[0239] In a preferred embodiment, a boron-containing NCA activator represented by the following formula may be used:
[0240] Z d + (A d- )
[0241] Wherein: Z is (LH) or a reducible Lewis acid, L is a neutral Lewis base; H is hydrogen; (LH) is a Bronsted acid; A d- is a boron-containing non-coordinating anion having a charge d-; d is 1, 2 or 3.
[0242] Cationic component Z d + Bronsted acids may be included, such as a proton or protonated Lewis base or a reducible Lewis acid capable of protonating or abstracting a moiety, such as an alkyl or aryl group, from a bulky ligand metallocene-containing transition metal catalyst precursor to yield a cationic transition metal species.
[0243] Active cation Z d + It can also be a structural part such as silver, (tropylium), carbon Ferrocene and mixtures, preferably carbon and ferrocene Most preferably, Z d + It is triphenyl carbon Preferred reducible Lewis acids can be any triarylcarbonyl (wherein the aryl group may be substituted or unsubstituted, such as those represented by the following formula: (Ar3C + ), wherein Ar is an aromatic group or is substituted by a heteroatom, C1-C 40 Hydrocarbon or substituted C1-C 40 Preferably, the reducible Lewis acid of "Z" includes those represented by the formula: (Ph3C), wherein Ph is a substituted or unsubstituted phenyl group, preferably a C1-C 40 Hydrocarbon substituted or substituted C1-C 40 Hydrocarbyl, preferably C1-C 20 Alkyl or aromatic group or substituted C1-C 20 Alkyl or aromatic group substituted, preferably, Z is triphenylcarbon
[0244] When Z d + It is an activating cation (LH) d + When it is preferably a Bronsted acid, it is capable of donating protons to the transition metal catalyst precursor to generate transition metal cations, including ammonium, oxygen phosphorus Silane and mixtures thereof, preferably ammonium amine, aniline, dimethylamine, diethylamine, N-methylaniline, diphenylamine, trimethylamine, triethylamine, N,N-dimethylaniline, methyldiphenylamine, pyridine, p-bromo-N,N-dimethylaniline, p-nitro-N,N-dimethylaniline; phosphorus derived from triethylphosphine, triphenylphosphine and diphenylphosphine From ethers such as dimethyl ether, diethyl ether, tetrahydrofuran and di Oxygen of alkane Sulfonium derived from thioethers, such as diethyl sulfide and tetrahydrothiophene, and mixtures thereof.
[0245] Anionic component A d- Including having the formula [M k+ Q n ] d-Those wherein k is 1, 2 or 3; n is 1, 2, 3, 4, 5 or 6 (preferably 1, 2, 3 or 4); nk = d; M is an element selected from Group 13 of the Periodic Table, preferably boron or aluminum, Q is independently hydrogen, bridged or unbridged dialkylamino, halo, alkoxy, aryloxy, hydrocarbon, substituted hydrocarbon, halocarbon, substituted halocarbon and halogenated hydrocarbon, said Q having up to 20 carbon atoms, provided that Q is halo not more than once. Preferably, each Q is a fluorinated hydrocarbon containing 1-20 carbon atoms, more preferably each Q is a fluorinated aryl, and most preferably each Q is a pentafluoroaryl. Suitable A d- Examples also include diboron compounds as disclosed in US Pat. No. 5,447,895, which is incorporated herein by reference in its entirety.
[0246] Illustrative, but non-limiting examples of boron compounds that can be used as activating co-catalysts are those described as activators (especially those specifically listed as activators) in US Pat. No. 8,658,556, which is incorporated herein by reference.
[0247] Most preferably, the ionic activator Z d + (A d- ) is one or more of the following: N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(perfluoronaphthyl)borate, N,N-dimethylanilinium tetrakis(perfluorobiphenyl)borate, N,N-dimethylanilinium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, triphenylcarbon tetrakis(perfluoronaphthyl)borate Tetrakis(perfluorobiphenyl) borate triphenylcarbon triphenylcarbonium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate or triphenylcarbonium tetrakis(perfluorophenyl)borate
[0248] Bulk activators can also be used as NCAs herein. "Bulk activator" as used herein refers to an anionic activator represented by the following formula:
[0249]
[0250]
[0251] Wherein: each R1 is independently a halogen group, preferably a fluoro group; Ar is a substituted or unsubstituted aryl group (preferably a substituted or unsubstituted phenyl group), preferably substituted with a C1-C 40 Hydrocarbyl, preferably C1-C 20 Alkyl or aromatic; each R2 is independently halogen, C6-C 20 Substituted aromatic hydrocarbon or -O-Si-R a silyloxy, where R aIt is C1-C 20 Hydrocarbyl or hydrocarbyl silyl (preferably R2 is fluoride or perfluorinated phenyl); each R3 is halogen, C6-C 20 Substituted aromatic hydrocarbon or -O-Si-R a silyloxy, where R a It is C1-C 20 A hydrocarbon group or a hydrocarbon silyl group (preferably, R3 is a fluoride ion or a C6 perfluorinated aromatic hydrocarbon group); wherein R2 and R3 may form one or more saturated or unsaturated substituted or unsubstituted rings (preferably, R2 and R3 form a perfluorinated phenyl ring); and L is a neutral Lewis base; (LH)+ is a Bronsted acid; d is 1, 2 or 3; wherein the anion has a molecular weight greater than 1020 g / mol; wherein at least three of the substituents on the B atom each have a molecular weight greater than 250 cubic Or more than 300 cubic meters Or more than 500 cubic meters The molecular volume of .
[0252] Preferably, (Ar3C) d + Yes (Ph3C) d + , wherein Ph is substituted, preferably unsubstituted, phenyl, preferably substituted with C1-C 40 Hydrocarbon or substituted C1-C 40 Hydrocarbyl, preferably C1-C 20 Alkyl or aromatic or substituted C1-C 20 Alkyl or aromatic group.
[0253] "Molecular volume" is used herein as an approximation of the spatial volume of an activator molecule in solution. Comparison of substituents having different molecular volumes allows substituents having smaller molecular volumes to be considered "less bulky" than substituents having larger molecular volumes. Conversely, substituents having larger molecular volumes can be considered "more bulky" than substituents having smaller molecular volumes.
[0254] Molecular volume can be calculated as reported in "A Simple "Back of the Envelope" Method for Estimating the Densities and Molecular Volumes of Liquids and Solids", Journal of Chemical Education, Vol. 71, No. 11, November 1994, pp. 962-964. Molecular volume (MV) (unit is cubic ) Use the formula: MV = 8.3Vs, where Vs is the scale volume. V s is the sum of the relative volumes of the constituent atoms and is calculated from the molecular formula of the substituent using the relative volumes in the table below. s 7.5% reduction / condensed ring.
[0255] element Relative volume H 1 The first short cycle, Li-F 2 The second short cycle, Na-Cl 4 The first long cycle, K-Br 5 The second longest period, Rb-I 7.5 The third longest period, Cs-Bi 9
[0256] For a list of particularly useful bulky activators, see US 8,658,556, which is incorporated herein by reference.
[0257] In another embodiment, one or more of the NCA activators are selected from the activators described in US Pat. No. 6,211,105.
[0258] Preferred activators include N,N-dimethylanilinium tetrakis(perfluoronaphthyl)borate, N,N-dimethylanilinium tetrakis(perfluorobiphenyl)borate, N,N-dimethylanilinium tetrakis(perfluorophenyl)borate, N,N-dimethylanilinium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, triphenylcarbonyl tetrakis(perfluoronaphthyl)borate, triphenylcarbonyl tetrakis(perfluorobiphenyl)borate, and triphenylcarbon tetrakis(3,5-bis(trifluoromethyl)phenyl)borate Triphenylcarbon tetrakis(perfluorophenyl)borate Me3NH+][B(C6F5)4-]; 1-(4-(tris(pentafluorophenyl)boronic acid)-2,3,5,6-tetrafluorophenyl)pyrrolidine salts; and tetrakis(pentafluorophenyl)boric acid and 4-(tris(pentafluorophenyl)boronic acid)-2,3,5,6-tetrafluoropyridine.
[0259] In at least one embodiment, the activator comprises a triarylcarbonyl (e.g. triphenylcarbon tetraphenylborate Triphenylcarbon tetrakis(pentafluorophenyl)borate Triphenylcarbon tetrakis(2,3,4,6-tetrafluorophenyl)borate Triphenylcarbon tetrakis(perfluoronaphthyl)borate Tetrakis(perfluorobiphenyl) borate triphenylcarbon triphenylcarbon tetrakis(3,5-bis(trifluoromethyl)phenyl)borate ).
[0260] In another embodiment, the activator includes one or more of the following: trialkylammonium tetrakis(pentafluorophenyl)borate, N,N-dialkylanilinium tetrakis(pentafluorophenyl)borate, N,N-dimethyl-(2,4,6-trimethylanilinium tetrakis(pentafluorophenyl)borate, trialkylammonium tetrakis(2,3,4,6-tetrafluorophenyl)borate, N,N-dialkylanilinium tetrakis(2,3,4,6-tetrafluorophenyl)borate, trialkylammonium tetrakis(perfluoronaphthyl)borate, N,N-dialkylanilinium tetrakis(perfluoronaphthyl)borate , trialkylammonium tetrakis(perfluorobiphenyl)borate, N,N-dialkylanilinium tetrakis(perfluorobiphenyl)borate, trialkylammonium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, N,N-dialkylanilinium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, N,N-dialkyl-(2,4,6-trimethylanilinium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, di(isopropyl)ammonium tetrakis(pentafluorophenyl)borate, (wherein the alkyl group is methyl, ethyl, propyl, n-butyl, sec-butyl or tert-butyl).
[0261] In a preferred embodiment of the present invention, N,N-dimethylanilinium tetrakis(perfluoronaphthyl)borate is the preferred activating agent.
[0262] Typical NCA activator to catalyst ratios, for example, all NCA activators to catalyst ratios are about 1: 1 molar ratios. Alternative preferred ranges include 0.1: 1-100: 1, or 0.5: 1-200: 1, or 1: 1-500: 1, or 1: 1-1000: 1. Particularly useful ranges are 0.5: 1-10: 1, preferably 1: 1-5: 1.
[0263] Activators useful herein also include those described in US Pat. No. 7,247,687 at column 169, line 50 to column 174, line 43, especially at column 172, line 24 to column 173, line 53.
[0264] It is also within the scope of the present disclosure that the catalyst compound may be combined with a combination of aluminoxane and NCA (see, for example, US 5,153,157, US 5,453,410, EP 0 573 120 Bl, WO 94 / 07928 and WO 95 / 14044 which discuss the use of aluminoxanes in combination with ionizing activators).
[0265] Nonessential scavengers or co-activators
[0266] In addition to the activator compound, a scavenger, chain transfer agent or co-activator may also be used. Alkyl aluminum or organoaluminum compounds that may be used as scavengers or co-activators include, for example, trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, tri-n-hexylaluminum, tri-n-octylaluminum and diethylzinc.
[0267] Useful chain transfer agents that can also be used herein are typically compounds represented by the formula AlR3, ZnR2 (wherein each R is independently a C1-C8 aliphatic group, preferably methyl, ethyl, propyl, butyl, phenyl, hexyl, octyl or isomers thereof) or combinations thereof, such as diethylzinc, trimethylaluminum, triisobutylaluminum, trioctylaluminum or combinations thereof.
[0268] In some embodiments, the catalyst compounds described herein can be loaded (with or without activators) by any method of effectively loading other coordination catalyst systems, effectively meaning that the prepared catalyst can be used to oligomerize or polymerize olefins in a multiphase process. Catalyst precursors, activators, co-activators if necessary, suitable solvents and carriers can be added in any order or simultaneously. Typically, the complex and activator can be combined in a solvent to form a solution. The carrier is then added and the mixture is stirred for 1 minute to 10 hours. The total solution volume can be greater than the pore volume of the carrier, but some embodiments limit the total solution volume to less than the volume required to form a gel or slurry (about 90%-400% of the pore volume, preferably about 100-200%). After stirring, the residual solvent is removed under vacuum, usually at ambient temperature and for more than 10-16 hours. But larger or smaller times and temperatures are possible.
[0269] The complex can also be supported in the absence of an activator; in that case, the activator (and, if desired, a co-activator) is added to the liquid phase of the polymerization process. In addition, two or more different complexes can be supported on the same support. Likewise, two or more activators or an activator and a co-activator can be supported on the same support.
[0270] Suitable solid particulate carriers are usually composed of polymers or high melting point oxide materials, each preferably porous. The carrier material can have an average particle size greater than 10 μm, so as to be used in the embodiments of the present disclosure. The VA carrier material can be a porous carrier material, for example, talc, inorganic oxides, inorganic chlorides (such as magnesium chloride) and resin carrier materials, such as polystyrene, polyolefins, or polymer composites or any other organic carrier materials, etc. The carrier material can be an inorganic oxide material, including metal or metalloid oxides of Groups -2, -3, -4, -5, -13 or -14. The catalyst carrier material can be silica, alumina, silica-alumina and mixtures thereof. Other inorganic oxides can be used alone or in combination with silica, alumina or silica-alumina. They are magnesium oxide, titanium oxide, zirconium oxide, etc. Lewis acidic substances such as montmorillonite and similar clays can also serve as carriers. In this case, the carrier can be optionally used as an activator component, however, additional activators can also be used.
[0271] The support material can be pretreated by a number of methods. For example, the inorganic oxide can be calcined, treated with a dehydroxylating agent such as aluminum alkyls and the like, or both.
[0272] As mentioned above, polymer supports will also be suitable in accordance with the present disclosure, see for example the descriptions in WO 95 / 15815 and US 5,427,991. The disclosed methods can be used with the catalyst complexes, activators or catalyst systems of the present disclosure to absorb or adsorb them on a polymer support, especially if composed of porous particles, or chemically bonded via functional groups bonded to or in the polymer chain.
[0273] Useful carriers usually have a range of 10-700 m 2 / g surface area, 0.1-4.0cc / g pore volume and 10-500μm average particle size. Some embodiments select 50-500m 2 / g surface area, 0.5-3.5cc / g pore volume or 20-200μm average particle size. Other embodiments select 100-400m 2 / g surface area, 0.8-3.0 cc / g pore volume and 30-100 μm average particle size. Useful supports typically have pore sizes of 10-1000 angstroms, or 50-500 angstroms, or 75-350 angstroms.
[0274] The catalyst complexes described herein are generally deposited on the support at a loading level of 10-100 micromoles of complex / gram of solid support; or 20-80 micromoles of complex / gram of solid support; or 40-60 micromoles of complex / gram of support. However, greater or lesser values may be used as long as the total amount of solid complex does not exceed the pore volume of the support.
[0275] In an alternative embodiment, the catalyst complexes and catalyst systems described herein can be present on a fluorinated support (e.g., a support that has been treated with at least one inorganic fluorine-containing compound, desirably, a particulate and porous support). For example, the fluorinated support composition can be a silica support in which a portion of the silica hydroxyl groups have been replaced with fluorine or a fluorine-containing compound. For example, a support useful herein is a silica support treated with ammonium hexafluorosilicate and / or ammonium tetrafluoroborate fluorine compounds. Typically, the fluorine concentration present on the support is in the range of 0.1-25 wt%, or 0.19-19 wt%, or 0.6-3.5 wt%, based on the weight of the support.
[0276] In one embodiment of the present disclosure, the catalyst system comprises fluorinated silica, an alkylaluminoxane activator, and a bridged monocyclopentadienyl Group 4 transition metal compound, wherein the fluorinated support is not calcined at a temperature of 400°C or higher.
[0277] The catalyst compound may be present on the support at 1-100 μmol / g supported catalyst, preferably 20-60 μmol / g supported catalyst.
[0278] The present disclosure also relates to a metallocene catalyst system comprising the reaction product of at least three components: (1) one or more bridged metallocenes having one tetrahydroindacene group; (2) one or more alkylaluminoxanes or NCA activators; and (3) one or more fluorinated support compositions, wherein the fluorinated support composition has not been calcined at a temperature of 400°C or higher, preferably, the fluorinated support composition has been calcined at a temperature of 100°C to 395°C, or 125°C to 350°C, or 150°C to 300°C.
[0279] Typically, the fluorinated supports described herein are prepared by combining a solution of a polar solvent (e.g., water) and a fluorinating agent (e.g., SiF4 or (NH4)2SiF6) with a slurry of the support (e.g., a toluene slurry of silica), followed by drying until it flows freely and, optionally, calcining (typically at a temperature in excess of 100°C for at least 1 hour). The support is then combined with an activator(s) and a catalyst compound (either alone or together).
[0280] For more information on fluorinated supports and methods for making them, see USSN 62 / 149,799, filed April 20, 2015 (and all cases claiming priority or benefit from USSN 62 / 149,799); USSN 62 / 103372, filed January 14, 2015 (and all cases claiming priority or benefit from USSN 62 / 103372); and PCT / US2015 / 067582, filed December 28, 2015, which are incorporated herein by reference.
[0281] Ethylene-based copolymers
[0282] The compositions of the present disclosure comprise ethylene-based copolymers. In at least one embodiment, the composition comprises a blend of a PEDM terpolymer and one or more ethylene-based copolymers.
[0283] The compositions of the present disclosure may include one or more ethylene-based copolymers in an amount from about 0 phr to about 99 phr, or from about 20 phr to about 99 phr, or from about 40 phr to about 99 phr, or from about 60 phr to about 99 phr, or from about 60 phr to about 95 phr, or from about 70 phr to about 95 phr, or from about 70 phr to about 10 phr, based on 100 parts of rubber as the total weight of PEDM and ethylene-based copolymers in the composition.
[0284] The ethylene-based copolymer may have an ethylene content of 40 wt% to 95 wt%, or 50 wt% to 90 wt%, or 55 wt% to 85 wt%, or 60 wt% to 75 wt%, based on the weight of the ethylene-based copolymer.
[0285] The ethylene-based copolymers of the present disclosure further comprise C3-C 12 α-olefin content and, optionally, polyene (preferably diene) content.
[0286] The ethylene-based copolymer may have a propylene content of 5 wt% to 60 wt%, or 10 wt% to 50 wt%, or 25 wt% to 50 wt%, or 5 wt% to 30 wt%, based on the weight of the ethylene-based copolymer. 12 α-olefins include propylene, butene, pentadiene, hexene, heptene, octene, nonene, decene, undecene, dodecene and their branched isomers. Propylene is particularly preferred according to some embodiments (e.g., the copolymer based on ethylene can be EP(D)M copolymer), while butene (1-butene) is preferred in other embodiments (e.g., the copolymer based on ethylene can be EB(D)M copolymer). In addition, in certain embodiments, the ethylene-based copolymer of the present disclosure can have an isotactic polypropylene content.
[0287] The ethylene-based copolymer may have a polyene content (preferably a diene content) of 0 wt% to 10 wt%, or 0.5 wt% to 5 wt%, or 5 wt% to 10 wt%, or 3 wt% to 7 wt%, based on the weight of the ethylene-based copolymer. Any polyene suitable in PEDM is suitable for inclusion in the ethylene-based copolymer, wherein VNB or ENB are preferred, especially ENB. According to other embodiments, suitable polyenes may include conjugated dienes. Conjugated dienes include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-di(C1-C5 alkyl)-1,3-butadiene, such as 2,3-dimethyl-1,3-butadiene, 2,3-diethyl-1,3-butadiene, 2-methyl-3-ethyl-1,3-butadiene or 2-methyl-3-isopropyl-1,3-butadiene, aryl-1,3-butadiene, 1,3-pentadiene or 2,4-hexadiene. Dienes also include vinyl aromatic compounds: styrene, o-, m- or p-methylstyrene, the "vinyltoluene" commercial mixtures, p-(tert-butyl)styrene, methoxystyrene, chlorostyrene, vinylmesitylene, divinylbenzene or vinylnaphthalene.
[0288] According to some embodiments, the ethylene-based copolymer exhibits a higher crystallinity than PEDM; for example, it can have Hf>1 J / g. According to still other embodiments, the crystallinity of the ethylene-based copolymer of the present disclosure can be expressed in terms of a percentage of crystallinity (i.e., % crystallinity), measured according to the DSC procedure described herein. The ethylene-based copolymer can have a % crystallinity of 1%-80%, such as 10%-60%, such as 20%-40%. (Crystallinity is determined by dividing the measured heat of fusion by the heat of fusion of 100% crystalline polyethylene, which has a value of 293 J / g (B. Wunderlich, Thermal Analysis, Academic Press, 1990, pp. 417-431)).
[0289] The ethylene-based copolymer may be an ethylene-propylene copolymer, in particular an EP(D)M terpolymer (e.g., VISTALON ® available from ExxonMobil). TM 706、VISTALON TM 2504 and Vistalon TM 7500, TAFMER available from Mitsui Chemicals TM ; or VERSIFY available from Dow Chemical TM ) or EB(D)M terpolymers. The ethylene-based copolymers of the present disclosure may have a weight average molecular weight (Mw) of 10,000 g / mol to 400,000 g / mol, or 100,000 g / mol to 200,000. They may also or alternatively have a melting point (DSC) of less than 110° C., or less than 100° C.
[0290] The compositions described herein may comprise a single ethylene-based copolymer or a mixture of two or more ethylene-based copolymers, which may be used in combination with any type of synthetic elastomer other than the ethylene-based copolymers, and even with polymers other than elastomers, such as thermoplastic polymers.
[0291] In at least one embodiment, the ethylene-based copolymer is a polyethylene-polybutadiene block copolymer, wherein the polyethylene-polybutadiene block copolymer is a block copolymer having the following general formula: PE—XL—fPB; wherein "PE" is a polyethylene block having a weight average molecular weight in the range of 1,000 to 150,000 g / mol, "fPB" is a functionalized polar polybutadiene block having a weight average molecular weight in the range of 500 g / mol to 30,000 g / mol, and "XL" is a cross-linking structural portion covalently connecting the PE and fPB blocks; wherein the maximum energy loss (tangent δ) of the immiscible polyolefin structural domain is at a temperature in the range of -30°C to 10°C.
[0292] In at least one embodiment, the composition of the present disclosure comprises 15 wt%-60 wt% of a styrenic copolymer; 1 wt%-60 wt% of a polybutadiene polymer; 1 wt%-60 wt% of a natural rubber or a synthetic polyisoprene; 15 wt%-60 wt% of a functionalized styrenic copolymer; 1 wt%-60 wt% of a functionalized polar polybutadiene polymer; or 1 wt%-60 wt% of a natural rubber or a functionalized synthetic polyisoprene.
[0293] Polymer blending
[0294] The compositions of the present disclosure can be formed by combining PEDM and ethylene-based copolymers using any suitable method known in the field of polymer processing. For example, the composition can be prepared by blending PEDM and ethylene-based copolymers in solution and generally removing the blend. Such polymer compositions have a predetermined amount of PEDM and ethylene-based copolymers and can be prepared by independent polymerization of the first and second elastomeric polymer components. Such separate polymerizations can be carried out in a series or parallel polymerization reactor or in a single polymerization reactor with at least two different polymerization catalysts. The recovery procedure for such a predetermined composition is described in U.S. Patent No. 4,722,971, which is incorporated herein by reference. The present disclosure includes traditional Ziegler-Natta catalyst systems, however, metallocene catalyst systems are also considered by the present disclosure.
[0295] In at least one embodiment, the method for preparing a composition of PEDM and ethylene-based copolymers includes contacting a first metallocene catalyst with ethylene, propylene, and a diene in a first reactor to form the PEDM. The method further includes contacting a second metallocene catalyst with ethylene and propylene and, optionally, a diene in a second reactor (or the first reactor) to form an ethylene-based copolymer. The method may include transferring the PEDM to the second reactor or transferring the ethylene-based copolymer to the first reactor, and recovering the mixture of the PEDM and the ethylene-based copolymer from the second reactor or the first reactor, respectively. The recovered polymer composition may then be crosslinked, for example, as described in more detail below.
[0296] Alternatively, in at least one embodiment, a blend of PEDM and an ethylene-based copolymer can be prepared by combining the PEDM from the first reactor and the ethylene-based copolymer from the second reactor and mixing, for example, in a production extruder such as on an injection molding machine or an extruder on a continuous extrusion line.
[0297] In at least one embodiment, the polymers may be blended in a batch mixer such as a BANBURY TM or BARBENDER TM The polymers are melt blended in a mixer. Blending can include melt blending the PEDM and ethylene-based copolymers in an extruder, such as a single screw extruder or a twin screw extruder. Extrusion techniques for polymer blends are well known in the art and are described in more detail in, for example, PLASTICS EXTRUSION TECHNOLOGY, F. Hensen, Ed. (Hanser, 1988), pp. 26-37 and POLYPROPYLENE HANDBOOK, EP Moore, Jr. Ed. (Hanser, 1996), pp. 304-348.
[0298] PEDM and ethylene-based copolymers may also be blended by a combination of methods including, but not limited to, solution blending, melt mixing, compounding in a shear mixer, and combinations thereof. For example, dry blending followed by melt blending in an extruder, or batch mixing of some components followed by melt blending with other components in an extruder. A double cone blender, a belt blender, or other suitable blender may also be used, or in a Farrel continuous mixer (FCM). TM ) PEDM and ethylene-based copolymers are blended.
[0299] PEDM, ethylene-based copolymers, and additives (eg, curatives, crosslinkers, fillers, processing oils, plasticizers, compatibilizers, crosslinkers, etc.) can be blended in different orders, which in some cases can alter the properties of the resulting composition.
[0300] In some cases, a masterbatch comprising PEDM, an ethylene-based copolymer, and additives (except a curative and a crosslinking agent) can be prepared at a first temperature. Then, a curative and / or a crosslinking agent can be mixed into the masterbatch at a second temperature lower than the first temperature.
[0301] In some embodiments, the masterbatch can be prepared by mixing the PEDM, ethylene-based copolymer, and additives (except curing agents and cross-linking agents) together in one step until the additives are incorporated (e.g., a homogenous blend is produced). This is referred to herein as a first pass process or first pass blending. After the first pass blending produces the masterbatch, the curing agent and / or cross-linking agent can be mixed into the masterbatch to produce the final blend.
[0302] In alternative embodiments, a two-step mixing method can be used to prepare a masterbatch. For example, in some embodiments, a masterbatch can be prepared by mixing an ethylene-based copolymer with additives (except for curing agents and cross-linking agents) until the additives are incorporated into the ethylene-based copolymer (e.g., to produce a uniform blend). The resulting blend is then mixed with PEDM and the curing agent and / or cross-linking agent. This is referred to herein as a second pass method or second pass blending. Alternatively, the curing agent and / or cross-linking agent can be mixed into the masterbatch after adding PEDM in the second pass to produce the final blend.
[0303] In some second-pass blending embodiments, mixing the ethylene-based copolymer / additive (except curatives and cross-linking agents) blend with PEDM can be performed in a mixer or other suitable system without removing the ethylene-based copolymer / additive blend from the mixer (i.e., first-pass blending) to produce a masterbatch. In alternative embodiments, the ethylene-based copolymer / additive (except curatives and cross-linking agents) blend can be removed from the mixer or other suitable system for producing the blend and then mixed with PEDM in a mixer or other suitable system (i.e., second-pass blending) to produce a masterbatch.
[0304] A homogeneous mixture can be achieved by mixing for a certain time, which corresponds to producing a homogeneous mixture. In some cases, the mixing parameters of the ethylene-based copolymer and the selected additive can be changed when a homogeneous mixture is obtained. For example, when carbon black (an exemplary filler) is mixed with an ethylene-based copolymer, the torque can reach a maximum steady state, where no significant increase in torque is observed to a minimum torque increase is observed.
[0305] Composition
[0306] The compositions of the present disclosure include and / or are the reaction products of the above-mentioned PEDM and ethylene-based copolymers (as polymer blends or otherwise) (and in any form: pellets, bundles or otherwise). As described above, the compositions of the present disclosure may further include and / or be the reaction products of any one or more additives (e.g., curing agents, crosslinking agents, fillers, processing oils, plasticizers, compatibilizers, crosslinking agents, etc.).
[0307] In embodiments where a curative, such as a crosslinking agent or a vulcanizing agent, is present in the composition, the polymers of the composition may be present in at least partially crosslinked form (i.e., at least a portion of the polymer chains are crosslinked with each other, for example, due to a curing process typical of EP(D)M rubbers). Accordingly, particular embodiments provide an at least partially crosslinked elastomeric composition prepared by mixing (according to any of the methods described above for polymer blends) a composition comprising: (a) PEDM and an ethylene-based copolymer; (b) one or more vulcanization activators; (c) one or more vulcanizing agents; and / or (d) one or more other additives.
[0308] Suitable vulcanization activators include zinc oxide, stearic acid, etc. These activators can be mixed in an amount of 0.1phr to 20phr. Different vulcanization activators can be present in different amounts. For example, when the vulcanization activator includes zinc oxide, zinc oxide can be present in an amount of 1phr to 20phr, or 2.5phr to 10phr (or, about 5phr), and stearic acid can be preferably used in an amount of 0.1phr to 5phr, or 0.1phr to 2phr, or about 1.5phr.
[0309] Any suitable vulcanizing agent known in the art may be used. Of particular note are the curing agents described in U.S. Pat. No. 7,915,354 at column 19, line 35 to column 20, line 30, which description is hereby incorporated by reference (e.g., sulfur, peroxide-based curing agents (VULCUP® available from Arkema of Colombes, France) and the like). TM 40KE), resin curing agents, silane and hydrosilane curing agents). Other examples include phenolic resin curing agents (e.g., described in U.S. Pat. No. 5,750,625, also incorporated herein by reference). Curing aids (e.g., zinc dimethacrylate (ZDMA) (DYMALINK TM 708, available from Cray Valley) or those described in the already incorporated description of U.S. Patent No. 7,915,354).
[0310] The additional additives may be selected from any known additives useful in EPDM compositions and may include in particular one or more of the following:
[0311] Process oils, such as paraffinic and / or isoparaffinic process oils (examples include Sunpartm 2280 (available from HollyFrontier Refining & Marketing LLC, Tulsa, Oklahoma); and FLEXON TM 876、CORE TM 600 base oil, FLEXON TM 815 and CORE TM 2500 base oil, available from ExxonMobil Chemical Company, Baytown, Texas. White oils (e.g., API Group II or Group III base oils) may be used as process oils, particularly in embodiments where the color of the final product may be important. Examples include paraffinic and / or isoparaffinic oils having low (less than 1 wt %, preferably less than 0.1 wt %) aromatic and heteroatom contents. The compositions of the present disclosure may contain 1 phr to 150 phr, or 50 phr to 100 phr, or 60 phr to 80 phr, or for sponge grades, 50 phr to 200 phr, or 70 phr to 150 phr, or 80 phr to 100 phr of process oil, and preferred process oils have a viscosity at 40° C. of 80 CSt to 600 CSt;
[0312] Vulcanization accelerators: The compositions of the present disclosure may contain 0.1 to 15 phr, or 1 to 5 phr, or 2 to 4 phr, where examples include thiazoles such as 2-mercaptobenzothiazole or mercaptobenzothiazole disulfide (MBTS); guanidines such as diphenylguanidine; sulfenamides such as N-cyclohexylbenzothiazolesulfenamide; dithiocarbamates such as zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, zinc dibenzyldithiocarbamate (ZBEC); and zinc dibutyldithiocarbamate, thioureas such as 1,3-diethylthiourea, thiophosphates, and the like;
[0313] Processing aids (e.g., polyethylene glycol or zinc soap);
[0314] Carbon black (e.g., having a particle size of 20 nm to 600 nm and a structure having a DBPA (dibutyl phthalate absorption value) of 0 to 150 as measured by the DBP method described in ASTM D2414). The composition of the present disclosure may contain 1 phr to 500 phr, preferably 1 phr to 200 phr, or 50 phr to 150 phr of carbon black;
[0315] Inorganic fillers (talc, calcium carbonate, clay, silica, aluminum trihydrate, etc.), which may be present in the composition at 1 to 200 phr, preferably 20 to 100 phr, or 30 to 60 phr;
[0316] When foaming may be desired, sponge or foam grade additives, such as blowing agents or foaming agents, especially in very high Mooney viscosity embodiments, such as those suitable for sponge grades. Examples of such agents include: azodicarbonamide (ADC), o-benzenesulfonyl hydrazide (OBSH), p-toluenesulfonyl hydrazide (TSH), 5-phenyltetrazole (5-PT), and sodium bicarbonate in citric acid. Microcapsules may also or instead be used for such foaming applications. These may include heat-expandable microspheres comprising a polymer shell containing a propellant. Examples are known in the art and described in, for example, U.S. Patent Nos. 6,582,633 and 3,615,972, WIPO Publication Nos. WO 99 / 46320 and WO 99 / 43758, and the contents of these documents are hereby incorporated by reference. Examples of such heat-expandable microspheres include EXPANCEL commercially available from Akzo Nobel NV. TM Products and ADVANCELL available from Sekisui TM In other embodiments, sponging or foaming can be achieved by injecting gas and / or liquid (e.g., water, CO2, N2) directly into the rubber in an extruder so that foaming occurs after the composition passes through the die; and
[0317] Various other additives may also be included, such as antioxidants (e.g., 1,2-dihydro-2,2,4-trimethylquinoline), stabilizers, preservatives, UV absorbers, antistatic agents, slip agents, moisture absorbers (e.g., calcium oxide), pigments, dyes, and other colorants.
[0318] The at least partially crosslinked polymer composition of the present disclosure is formed by mixing the above components in any suitable manner as described in the polymer blending section above, such as a Banbury mixer. Mixing in these embodiments may include any one or more typical mixing methods used for EP(D)M compositions, such as open mill mixing, mixing using an internal mixer or kneader, and extrusion (e.g., via a twin screw extruder).
[0319] In addition, in some embodiments, additives can be incorporated into the polymer blend directly or as part of a masterbatch (i.e., an additive package containing several additives to be added at a predetermined ratio). The masterbatch can be added in any suitable amount. For example, a masterbatch containing additives can be used in an amount of about 0.1 to about 10wt%, or about 0.25 to about 7.5wt%, or about 0.5 to about 5wt%, or about 1 to about 5wt%, or about 2 to about 4wt%, based on the total weight of the polymer blend and the masterbatch. This is a common practice in polymer processing and is typically used to add pigments, additives, and fillers to the final composition. The dispersion (or "thinning") of the masterbatch can be performed as part of a process step for manufacturing an article, such as in an extruder on an injection molding machine or a continuous extrusion line, or during an independent compounding step.
[0320] The compositions described herein comprising PEDM and ethylene-based copolymers may have a raw rubber to rubber adhesion of 20 g-force / inch width or greater, or from 20 g-force / inch width to 6000 g-force / inch width, or from 50 g-force / inch width to 5000 g-force / inch width after blending. The compositions described herein comprising PEDM and ethylene-based copolymers may have a raw rubber to rubber adhesion of 20 g-force / inch width or greater, or from 20 g-force / inch width to 6000 g-force / inch width, or from 50 g-force / inch width to 5000 g-force / inch width after aging at room temperature for 1 month. The compositions described herein comprising PEDM and ethylene-based copolymers may have a raw rubber to rubber adhesion retention percentage (aged force divided by blended force multiplied by 100) from blending to aging at room temperature for 1 month of 20% to 250%, or from 30% to 150%, or from 30% to 100%, or from 50% to 250%. A bond retention of 200% means that the bond doubles with aging.
[0321] The compositions described herein comprising PEDM and ethylene-based copolymers can have a raw rubber to polar substrate adhesion of 10 g-force / inch width or greater, or 10 g-force / inch width to 500 g-force / inch width, or 10 g-force / inch width to 400 g-force / inch width, or 10 g-force / inch width to 300 g-force / inch width, or 10 g-force / inch width to 200 g-force / inch width, or 20 g-force / inch width to 200 g-force / inch width after blending. The polar substrate can include any suitable material, such as one or more of cotton, rayon, polyamide, polyester, polycarbonate, aramid, steel, aluminum, glass, carbon, polyketone, basalt, boron, and oriented non-continuous fibers, which are used to make rubber parts, such as rubber parts for reinforcement.
[0322] Rubber to rubber and rubber to polar substrate adhesion tests can be measured based on modified ASTM D3330 / D330M-04 (2010) Methods B and F. This method offers the benefits of a larger test range and longer dwell time, thus providing larger scale testing of samples for the Tel-Tak method.
[0323] tape
[0324] The compositions of the present disclosure may be used as one or more components of a drive belt (eg, a V-belt, a flat belt, a toothed or synchronous belt, or a multi-ribbed belt) and / or a conveyor belt.
[0325] Figure 1 is a fragmentary perspective view of a drive belt according to some embodiments of the present disclosure. Figure 1As shown, the synchronous belt 100 includes an elastic main body 102 and a pulley contact portion 104 arranged along the inner edge of the main body 102. The main body 102 includes a composition including one or more PEDMs of the present disclosure. The pulley contact portion 104 is configured to form alternating transverse protrusions 106 and grooves 108, which are configured to couple with transverse groove wheels or sprockets. A tensile layer 110 is arranged in the main body 102 to provide support and strength for the belt 100. The tensile layer 110 includes a plurality of tensile cables 112 arranged longitudinally along the length of the main body 112. The cables 112 include any suitable material, such as one or more of cotton, rayon, polyamide, polyester, aramid, steel, aluminum, glass, carbon, polyketone, basalt, boron, polycarbonate, or non-continuous fibers oriented for low load capacity. The cables 112 may be untreated or have a surface treatment. The surface treatment may be a coating physically on the surface of the cables 112 or chemically bonded to the surface of the cables 112. The term "coating" as used herein does not mean 100% coverage, but can be any amount of coverage. Physical or chemical coatings are used to enhance the adhesion or bonding between a generally polar cable and a generally non-polar rubber. Examples of coatings on the surface of the cable 112 can include, but are not limited to, polymers or small molecules that are dipped, sprayed, or extruded on the surface. For example, polymers containing amine or amide structural moieties can be chemically bonded to the hydroxyl groups of rayon and polyester cables. Heat can be used to promote the chemical reaction between the cable surface and the coating. Optionally, PEDM (e.g., the PEDM described herein) can be a component of a coating that optionally has an ethylene-based copolymer (e.g., the ethylene-based copolymer described herein). For example, the PEDM component in the coating can be a PEDM terpolymer in an amount of 1 phr to 100 phr, which contains 59 wt% to 99 wt% propylene, 1 wt% to 41 wt% α-olefins, and 0.5 wt% to 20 wt% dienes, the wt% being based on the weight of the PEDM terpolymer. The ethylene-based copolymer component in the coating can be an ethylene-based copolymer in an amount of 0 phr to 99 phr, comprising 40 wt% to 95 wt% ethylene, 5 wt% to 60 wt% alpha-olefin, and 0 wt% to 10 wt% diene, the wt% being based on the weight of the ethylene-based copolymer. The PEDM terpolymer and ethylene-based copolymer in the coating do not necessarily have to be the same as the PEDM terpolymer and ethylene-based copolymer in the composition described herein (e.g., a PEDM terpolymer optionally having an ethylene-based copolymer).
[0326] The reinforcing fabric 114 is arranged on the protrusion 106 and the groove 108 and forms the pulley contact portion. The reinforcing fabric 114 can have any suitable configuration, such as a conventional woven fabric composed of warp and weft at a certain angle, or can include warps bound together by spatial pick-up lines, or a knitted or woven configuration, or a non-woven fabric. Suitable fabrics include one or more of cotton, polyester, polyamide, polycarbonate, acrylic resin, aromatic polyamide, polyketone, hemp, jute or glass fiber. The fabric 114 can be untreated or have a surface treatment. The surface treatment can be a coating that is physically on the surface of the fabric 114 or chemically bonded to the surface of the fabric 114. The term "coating" used herein does not mean 100% coverage, but can be any amount of coverage. Physical or chemical coatings are used to enhance the adhesion or bonding between a generally polar fabric and a generally non-polar rubber. Examples of coatings on the surface of the fabric 114 can include, but are not limited to, polymers or small molecules that are calendered, extruded, dipped or sprayed on the surface. For example, a polymer comprising an amine or amide moiety can be chemically bonded to the hydroxyl groups of a polyester fabric. Heat can be used to promote a chemical reaction or physical bonding between the fabric surface and the coating. Optionally, a PEDM (e.g., a PEDM described herein) can be a component of a coating that optionally has an ethylene-based copolymer (e.g., an ethylene-based copolymer described herein). For example, the PEDM component in the coating can be a PEDM terpolymer in an amount of 1 phr to 100 phr, comprising 59 wt% to 99 wt% propylene, 1 wt% to 41 wt% α-olefins, and 0.5 wt% to 20 wt% diene, the wt% being based on the weight of the PEDM terpolymer. The ethylene-based copolymer component in the coating can be an ethylene-based copolymer in an amount of 0 phr to 99 phr, comprising 40 wt% to 95 wt% ethylene, 5 wt% to 60 wt% α-olefins, and 0 wt% to 10 wt% diene, the wt% being based on the weight of the ethylene-based copolymer. The PEDM terpolymer and ethylene-based copolymer in the coating do not necessarily have to be the same as the PEDM terpolymer and ethylene-based copolymer in the compositions described herein (eg, a PEDM terpolymer optionally with an ethylene-based copolymer).
[0327] Figure 2 is a fragmentary perspective view of a drive belt according to another embodiment of the present disclosure. Figure 2As shown, the toothed V-belt 200 includes an elastomeric portion 202 and a tensile layer 204 including a cord 206. The body portion 202 includes one or more compositions of the present disclosure (compositions containing PEDM). The cord 206 includes any suitable material, such as one or more of cotton, rayon, polyamide, polyester, aramid, steel, aluminum, glass, carbon, polyketone, polycarbonate, basalt, boron or non-continuous fibers oriented for low load capacity. The V-belt 200 includes a pulley contact portion 208, which has two juxtaposed sides of the belt designed to be inserted into a V-shaped pulley. The V-belt 200 includes grooves 210 and protrusions 212. Included in the V-belt category are those V-belts designed for continuously variable transmission ("CVT") applications, which typically display a belt body that is relatively wider than the belt thickness.
[0328] Figure 3 is a fragmentary perspective view of a drive belt according to one embodiment of the present disclosure. Figure 3 As shown, the multi-V-ribbed belt 300 includes a main body 302 and a tensile reinforcement member 304 including a cable 306. The main body 302 includes one or more compositions of the present disclosure (compositions containing PEDM). The longitudinal groove pulley contact portion 308 includes a plurality of protrusions 310 alternating with a plurality of grooves 312, which together define a drive surface 314 of the belt 300. Figure 1 , Figure 2 and Figure 3 In each of these examples, the corresponding pulley contact portion and the corresponding body portion can be coupled / coupled and can be formed of the same material or layered with different materials.
[0329] The conveyor belt can be manufactured as a layered composition of a calendered sheet of the present disclosure composition comprising PEDM and an ethylene-based copolymer and a reinforcing fabric. For example, Figure 4 An exemplary conveyor belt construction 400 is shown, which includes, in order, (a) a cover rubber layer 402, (b) alternating fabric 404 and rubber skin layers 406, and (c) a bottom rubber layer 408. Other layers may be included in other conveyor belt constructions. The cover rubber layer 402, the rubber skin layer 406, and / or the bottom rubber layer 408 include one or more compositions of the present disclosure including PEDM and an ethylene-based copolymer.
[0330] The reinforcement fabric 404 may have any suitable configuration such as a conventional woven fabric consisting of warp and weft threads at an angle, or may include warp threads bound together by space pick-up threads, or a knitted or woven configuration, or a nonwoven fabric. Suitable fabrics include one or more of cotton, polyester, polyamide, acrylic resin, aramid, polyketone, polycarbonate, hemp, jute, or fiberglass.
[0331] Conveyor belts are usually manufactured by laminating the above layers (or other desired layer sequences) using a calendering process. The calendered layered structure is then cured. The high adhesion in the rubber layer improves the fusion between adjacent layers and reduces bubble formation between layers.
[0332] exist Figure 1 , Figure 2 , Figure 3 and Figure 4 In each of the exemplary belt embodiments shown, the composition of the present disclosure (containing the PEDM composition) forming the main belt body may further comprise any suitable polymer. Suitable additional polymers include polyurethane elastomers (also including polyurethane / urea elastomers and so-called ground rubber) (PU), polychloroprene rubber (CR), acrylonitrile butadiene rubber (NBR), hydrogenated NBR (HNBR), styrene-butadiene rubber (SBR), alkylated chlorosulfonated polyethylene (ACSM), polyepichlorohydrin, polybutadiene rubber (BR), natural rubber (NR), and ethylene alpha-olefin elastomers such as ethylene propylene copolymers (EPM), ethylene propylene diene terpolymers (EPDM), ethylene octene copolymers (EOM), ethylene butene copolymers (EBM), ethylene octene terpolymers (EODM); ethylene butene terpolymers (EBDM); ethylene vinyl acetate elastomers (EVM); ethylene methacrylate (EAM); and silicone rubber.
[0333] To form the elastomeric body portion of the belt according to at least one embodiment of the present disclosure, the polymers may be blended according to known mixing methods and blended with general rubber compounding ingredients as described above, including but not limited to fillers, plasticizers, stabilizers, vulcanizers / curing agents, adjuvants and accelerators in conventionally employed amounts.
[0334] hose
[0335] The hose can be manufactured as a layered composition by extruding the composition of the present disclosure comprising PEDM and an ethylene-based copolymer. Figure 5 An example hose construction 500 is shown, which includes, in order, (a) an inner rubber tube 502, (b) a reinforcing fabric 504, and (c) an outer rubber layer 506. Other layers may be included in other hose constructions. The inner rubber tube 502 and / or the outer rubber layer 506 may include one or more compositions of the present disclosure comprising PEDM and an ethylene-based copolymer.
[0336] The reinforcing fabric 504 may have any suitable configuration such as a conventional woven fabric consisting of warp and weft threads at an angle, or may include warp threads bound together by space pick-up threads, or a knitted or woven configuration, or a nonwoven fabric. Suitable fabrics include one or more of cotton, polyester, polyamide, acrylic resin, aramid, polycarbonate, polyketone, hemp, jute, or fiberglass.
[0337] The hose is typically manufactured by extruding an inner rubber tube 502, covering the inner rubber tube 502 with a reinforcing fabric 504, and extruding an outer rubber layer 506 onto the reinforcing fabric 504. High adhesion in the rubber layers improves fusion between adjacent layers and reduces bubble formation between layers.
[0338] roof
[0339] Various roofing materials can be made by extruding the disclosed compositions comprising PEDM and ethylene-based copolymers. Such materials can benefit from improved adhesion and retention of physical properties, especially when compared to formulations comprising conventional hydrocarbon tackifying resins.
[0340] An exemplary roofing material application of the compositions disclosed herein is a roofing membrane. The roofing membrane can be a single layer or multilayer structure, optionally including fiber or cord curtain reinforcement. Advantageously, in some embodiments, a composition comprising PEDM and an ethylene-based copolymer (such as EPDM) is extruded as a layer to form a portion of a roofing material. Such a roofing membrane improved by using a composition comprising a PEDM polymer disclosed herein can have improved adhesion while improving or maintaining the rheology or physical properties of the composition.
[0341] Other machine-made products
[0342] The composition of the present disclosure can be used as one or more components of industrial and garden hoses, sponge parts molded and extruded, and gaskets and seals. In such components, the composition of the present disclosure (comprising PEDM, based on ethylene copolymers and optionally, one or more additives) can adhere to another polymer composition comprising cotton, rayon, polyamide, polyester, aramid, steel, aluminum, glass, carbon, polyketone, polycarbonate, basalt and boron, which can be in the form of film, belt, hose, tire, woven fabric or nonwoven fabric. Due to the enhanced adhesion properties of the composition of the present disclosure, the adhesion of the aforementioned materials can be significantly better than the adhesion between EP (D) M and the material. For example, the adhesion between the film of the composition of the present disclosure and the film / substrate of polycarbonate, aluminum or stainless steel can have the rubber and substrate adhesion exceeding 10gm force / inch width. In addition, polycarbonate, aluminum or stainless steel fiber / substrate can adhere to the composition of the present disclosure more strongly than independent EP (D) M. Example
[0343] Mooney viscosity (ML) can be measured by ASTM D1646-17 ((1+4), 125°C, 2s -1 Ethylene content was determined using FTIR according to ASTM D3900 and was not corrected for diene content. ENB was determined using FTIR according to ASTM D6047.
[0344] Molecular Weight Determination by Polymer Char GPC-IR with Multi-Detector
[0345] Unless otherwise stated, the distribution and fraction of molecular weight (number average molecular weight (Mn), weight average molecular weight (Mw) and z average molecular weight (Mz), Mw / Mn, etc.) are determined by using a high temperature gel permeation chromatography (Polymer Char GPC-IR) equipped with a multi-channel infrared detector IR5 based on a bandpass filter, an 18-angle Wyatt Dawn Heleos light scattering detector and a 4-capillary viscometer with a Wheatstone bridge configuration. Three Agilent PLgel 10μm mixed-B LS columns are used to provide polymer separation. Aldrich reagent grade 1,2,4-trichlorobenzene (TCB) containing 300ppm antioxidant butylated hydroxytoluene (BHT) is used as the mobile phase. The TCB mixture is filtered through a 0.1μm Teflon filter and degassed with an online degasser before entering the GPC instrument. The nominal flow rate is 1.0ml / min and the nominal injection volume is 200μL. The entire system including the transfer line, column and viscometer detector was loaded in an oven maintained at 145°C. The polymer sample was weighed and sealed in a standard vial, to which 80 μL of flow marker (heptane) was added. After the vial was loaded into the autosampler, the polymer was automatically dissolved in the instrument with 8 mL of added TCB solvent. For polypropylene samples, the polymer was dissolved by continuous shaking at 160°C for about 2 hours. The concentration (c) of each point in the chromatogram was calculated by the IR5 broadband signal intensity (I) minus the baseline using the following equation: c=βI, where β is the mass constant. Mass recovery is calculated by the ratio of the integrated area of the concentration chromatogram to the elution volume and the injection mass is equal to the predicted measured concentration multiplied by the injection loop volume. Conventional molecular weight (IR MW) was determined by combining a universal calibration relationship with a column calibration performed with a series of 700-10M gm / mole monodisperse polystyrene (PS) standard samples. The MW at each elution volume was calculated using the following equation:
[0346]
[0347] The variables with the subscript "PS" represent polystyrene, while those without the subscript represent the test sample.PS =0.67 and K PS =0.000175, while for other materials, α and K are calculated from empirical formulas (Sun, T. et al., Macromolecules 2001, 34, 6812). Here, unless otherwise specified, concentrations are expressed in g / cm 3 The molecular weight is expressed in g / mole and the intrinsic viscosity (and hence K in the Mark-Houwink equation) is expressed in dl / g.
[0348] The LS molecular weight (M) at each point in the chromatogram was determined by analyzing the LS output using the Zimm model of static light scattering.
[0349]
[0350] Here, ΔR(θ) is the excess Rayleigh scattering intensity measured at the scattering angle θ, c is the polymer concentration determined by IR5 analysis, A2 is the second virial coefficient, P(θ) is the shape factor of the monodisperse random coil, and K o is the optical constant of the system:
[0351]
[0352] Where N A is Avogadro's constant and (dn / dc) is the refractive index increment of the system. The refractive index of TCB at 145°C and λ=665 nm is n=1.500. For the purposes of this disclosure and the claims thereto, for ethylene-propylene copolymers, (dn / dc)=0.1048 and for EPDM containing ENB as the diene, (dn / dc)=0.1048-0.0016ENB, where ENB is the ENB content (in wt%) in the ethylene-propylene-diene terpolymer. In the case where other non-conjugated polyenes are used instead of ENB (or in addition to ENB), the ENB value is taken as the weight percentage of the total non-conjugated polyenes.
[0353] The specific viscosity is determined using a high temperature polymer Char viscometer with four capillaries arranged in a Wheatstone bridge configuration and two pressure sensors. One sensor measures the total pressure drop across the detector and the other, located between the two sides of the bridge, measures the differential pressure. The specific viscosity η of the solution flowing through the viscometer is s The intrinsic viscosity [η] at each point in the chromatogram is calculated from their output. s / c is calculated where c is the concentration and is determined from the IR5 broadband channel output.
[0354] The glass transition temperature (Tg), melting temperature (Tm) and heat of fusion (Hf) of the polymer were determined using a TA Instruments model Q200 machine according to ASTM D3418-03 using differential scanning calorimetry (DSC). Samples weighing approximately 5-10 mg were kept in an aluminum sample pan and air-sealed. They were gradually heated to 200°C at a rate of 10°C / min, and then kept at 200°C for 2 minutes. They were subsequently cooled to -90°C at a rate of 10°C / min and kept isothermally at -90°C for 2 minutes. This was followed by a second heating cycle in which the sample was heated to 200°C at 10°C / min. The first and second cycle thermal results were recorded.
[0355] Unless otherwise stated, during the second heating cycle, the appearance of melting indicates crystallinity and the heat of fusion so measured is used to calculate crystallinity. The exotherm (recorded as the area under the sample melting peak) is a measure of the heat of fusion and can be expressed in joules per gram of polymer. The melting point is recorded as the maximum endothermic temperature within the melting range of the sample relative to the baseline measurement of the temperature-dependent incremental heat capacity of the polymer.
[0356] The percentage crystallinity was calculated using the following formula: [area under the curve (in J / g) / H o (in J / g)]×100, where H o It is the ideal heat of fusion of a perfect crystal of a homopolymer of the major monomer component. o These values are taken from Polymer Handbook, 4th edition, published by John Wiley and Sons, New York 1999, except that a value of 290 J / g is used for H o (Polyethylene), value H of 140 J / g o (polybutene), a value of 207 J / g is used for H o (Polypropylene).
[0357] The Tg was determined from the second heating cycle of DSC.
[0358] The cryoprobe was operated with a field strength of at least 600 MHz in a solvent mixture of ODCB (o-dichlorobenzene) and benzene-d6 (C6D6) (90:10) at 120 °C with a flip angle of 90° and inversion gated decoupling of 20 s delay. 13 C solution NMR. Sample preparation (polymer dissolution) was performed at 140° C., where 0.20 grams of polymer was dissolved in the appropriate amount of solvent to obtain a final polymer solution volume of 3 ml. Chemical shifts were referenced to the solvent signal at 127.2 ppm.
[0359] The tacticity is calculated by integrating the CH3 region of the propylene unit, wherein the region is defined as:
[0360] mm area 21.20-20.5ppm mr area 20.5-19.75ppm rr area 19.75-18.7ppm
[0361] To take into account the overlap of the EP sequences in the mr and rr regions, the EPE and EPP contributions were removed using the CH EPE peak at 32.8 ppm and the CH EPP peak at 30.5 ppm.
[0362] mm area 21.20-20.5ppm mr area (20.5-19.75ppm-CH EPP) rr area (19.75-18.7ppm-CH EPE)
[0363] The sum of the integrals of the mm, mr and rr regions or the "total" is used to calculate the percentages of mm, mr and rr triads, where "total" = mm + mr + rr.
[0364] %mm=mm×100 / total
[0365] %mr=mr×100 / total
[0366] %rr=rr×100 / total
[0367] Regio defects and ENB sequence effects were not considered in the tacticity calculations. Their contributions were assumed to be negligible.
[0368] The dyad m and r percentages are calculated as follows:
[0369] m=%mm+(0.5×%mr)
[0370] r = %rr + (0.5 x %mr).
[0371] The "propylene stereoregularity index" (expressed herein as [m / r]) is calculated from the above-corrected integrated area. When [m / r] is 0 to less than 1.0, the polymer is generally described as syndiotactic, when [m / r] is 1.0, the polymer is atactic, and when [m / r] is greater than 1.0, the polymer is generally described as isotactic.
[0372] The EP(D)M polymer used is VISTALON TM 706, which is an ethylene-propylene copolymer having a Mooney viscosity (ML, 1+4@125°C) of 42MU and an ethylene content of 65 wt%; VISTALON TM 7500, which is an ethylene-propylene-diene terpolymer having a Mooney viscosity (ML, 1+4@125°C) of 91MU, an ethylene content of 56 wt% and an ENB content of 5.7%; VISTALON TM 2504, which is an ethylene-propylene-diene terpolymer having a Mooney viscosity (ML, 1+4@125°C) of 25MU, an ethylene content of 58 wt% and an ENB content of 4.7%, and VISTALONTM 9301, which is an ethylene-propylene-diene terpolymer having a Mooney viscosity (ML, 1+4@125°C) of 67MU, an ethylene content of 69 wt% and an ENB content of 2.8%, as shown in the following table. The PEDM polymer is prepared by the polymerization process described in PCT / US2019 / 022738 filed on March 18, 2019 and PCT / US2019 / 022764 filed on March 18, 2019, the disclosures of which are incorporated herein in their entirety.
[0373] Table 1 shows the polymer properties of several PEDM polymers used to prepare various compounds.
[0374] Table 1 - PE(D)M polymers
[0375]
[0376] *Hf of Samp-11 was still 0 J / g (not detectable) after DSC experiment followed by aging for 3 months at room temperature, as measured from the first heating cycle.
[0377] Table 1 - PE(D)M polymers (continued)
[0378]
[0379] Using Vistalon TM 706 and Vistalon TM 2504 was used as the EPDM base polymer to formulate compositions suitable for drive belt applications. Table 2 shows the peroxide cured EPDM belt formulations used in the examples. The control formulation contained Vistalon TM 706 or Vistalon TM 2504EP(D)M. The polymer content was 100 phr, which included both the EPDM control polymer and the PEDM; that is, a portion of the EPDM was replaced by the PEDM polymer at a level of 20, 30 or 100 phr. One or two PEDM polymers were used in the formulation. Compounding was performed in a Banbury OOC mixer with a mixer volume of 4.3 L. The fill factor was 70%. The masterbatch formulation excluding the curing agent was prepared at 50 rpm in the first pass with a scan at 140°F, a scan at 200°F, and a scan at 240°F, and the plunger was 60 psi. The average batch discharge temperature from the first pass of the mixer was about 300°F. The curing agent was added in the second pass to complete the compound.
[0380] Table 2. Tape preparation and mixing
[0381] Components PHR polymer 100 Black 330 60 Dymalink 708(ZDMA)_ 15 Sunpar 2280 10 Zinc Oxide 5.0 Zinc stearate 2.0 Agerite Resin D 1.0 Grind Addition (Whole Batch) Vulcup 40 KE 5.0 Dymalink 719 0.3
[0382] In Table 2, "Polymer" refers to the corresponding amount of EP(D)M plus PEDM polymer; Black 330 is carbon black (available in pellet form from Cabot); SUNPAR TM 2280 is a paraffin processing oil; zinc stearate and ZnO (zinc oxide) are vulcanization activators; AGERITE TM Resin D TM is the antioxidant 1,2-dihydro-2,2,4-trimethylquinoline (available from Vanderbilt Chemicals); DYMALINK TM 708(ZDMA) and DYMALINK TM 719 are each vulcanization activators; VULCUP TM 40KE is an organic peroxide vulcanizing / crosslinking agent.
[0383] Using Vistalon TM 7500 is used as the EPDM base polymer to formulate a composition suitable for hose applications. The polymer content is 100 phr, which includes Vistalon TM 7500 polymer and PEDM; i.e., Vistalon TM A portion of the 7500 EPDM was replaced with PEDM polymer at 10 or 20 phr levels. Compounding was performed in a Banbury OOC mixer with a mixer volume of 4.3 L. The fill factor was 70%. Masterbatch formulations excluding curing agent were prepared in the first pass as described in Table 3. The average batch discharge temperature from the mixer was about 300°F. Curing agent was added in the second pass to complete the compound.
[0384] Table 3. Hose Formulation and Mixing
[0385]
[0386] Using Vistalon TM 9301 is used as EPDM base polymer to formulate compositions suitable for roof applications. The polymer content is 100 phr, which includes Vistalon TM 9301 polymer and PEDM; i.e., Vistalon TMA portion of the 9301 EPDM was replaced with PEDM polymer at 5, 10 or 20 phr levels. Compounding was performed in a Banbury OOC mixer with a mixer volume of 4.3 L. The fill factor was 70%. Masterbatch formulations excluding curing agent were prepared in the first pass as described in Table 3. The average batch discharge temperature from the mixer was about 300°F. Curing agent was added in the second pass to complete the compound.
[0387] Table 4. Roof Formulations and Mixings
[0388]
[0389] In Table 4, Escorez TM 1102 is a tackifier with a low molecular weight (available from ExxonMobil); Sulfur-80 is a curing agent; MBTS, TMTD-75 and Butyl Zimate are vulcanization accelerators.
[0390] The formulations were compression molded and tested for various physical properties using appropriate ASTM methods. Compound M1 at 100°C was measured by ASTM D1646-17 method. Mooney scorch was measured according to ASTM D1646-17 test method. Moving die rheometer (MDR) was measured by ASTM D5289 method. Mechanical properties, including hardness, tensile strength, elongation, and green strength, were measured by ASTM D412 method. Compression set was measured by ASTM D395-B method. Die C tear strength was measured by ASTM D624 method. Tensile and elongation after oil aging were measured by ASTM D471 method.
[0391] The rubber-to-rubber adhesion / green adhesion test was conducted based on a modified ASTM D3330 / D330M-04 (2010) method B and F. This modified method employs elements of methods B and F within the parameters of the standard. Method B requires application to the material of interest instead of stainless steel. Method F requires a 90° angle for thicker, more rigid backings. Specifically, the following modifications to the ASTM method were utilized: (1) instead of a 2 μm finish stainless steel substrate according to the ASTM method, an uncured rubber sheet specimen (top sample) and a test substrate of the same rubber being tested (bottom sample) or a polycarbonate, stainless steel, and aluminum (2 inch x 6 inch) substrate were used; (2) for conditioning, instead of 24 hours at 23°C as in the ASTM method, the specimens were tested at ambient conditions; (3) unless otherwise noted, the default dwell time was 1 minute. Average adhesion values of about 5 to 10 replicates were reported, with typical coefficients of variation of about 20% or less.
[0392] Rubber to rubber / green bond testing of belt compounds was performed using calendered EPDM / PEDM compound samples. The EPDM / PEDM compounds were initially ground on a 10-inch x 20-inch roll mill manufactured by Kobelco Stewart Bolling, Inc. (KSBI). The roll temperature of the rear roll was set at 180°F and the roll temperature of the front roll was set at 170°F. The compounds were sent hot to the calender for processing. Calendered samples were prepared on a laboratory three-roll 6-inch x 13-inch calender at KSBI. For EPDM / PEDM materials; the top roll was set at 180°F, the middle roll was set at 150°F, and the bottom roll was maintained at room temperature. The target gauge thickness was set between 30-40 gauge (0.030-0.040 inches).
[0393] Rubber to rubber / green bond testing of hose compounds was performed using extruded EPDM / PEDM compound samples. Extruded EPDM / PEDM compound samples were prepared using a Haake polylab system. The Haake polylab system consists of a Rheocord that drives and controls the measuring sensors, which are the extruder (which is called Rheomex) and the post-extrusion equipment. The temperature zones were set as follows: throat (70°C), barrel (80°C), screw (80°C) and die (90°C). The extrusion rate was set to 30rpm. The target gauge thickness was set between 30-40 gauge (0.030-0.040 inches).
[0394] The test substrate can be composed of 2 inches by 6 inches of uncured rubber compound or other polar substrates as described above. Test strips or specimens of the same compound are backed with 1 inch by 6 inches of non-extensible tape. As described in the method, the rubber is applied to the rubber / polar substrate using a Cheminstruments RD-3000 automatic roller press with a 4.5 pound roller for consistent application of 2 cycles of rolling. After 1 minute of contact (dwell time), the bonded strips are removed and the removal force is measured on a Cheminstruments AR-2000-Adhesion / Peel Tester while maintaining a 90° peel. The removal rate is 1 inch / minute. The measured bond area is 3 inches 2 , with about 1000 data points. Low adhesion compounds may not maintain a 90° angle. This method has a detection limit of about 5 gm / inch. Substrates of polycarbonate (Bayer Markolon Polycarbonate Plastic), stainless steel (304 stainless steel 2μ finish), and aluminum (Q-Panel Bare Aluminum 3003H14 alloy) were purchased from Chemins truments.
[0395] Table 5 shows the properties of the tape compounds. In general, E1.1, E1.2 and E1.3 showed a better balance of adhesion and cure / physical properties (e.g., state of cure (MH-ML), modulus after cure and tear strength) than C1.1, C1.2, C1.3 and C1.4.
[0396] Table 5: Tape Compound Properties
[0397]
[0398] The properties of the hose compounds are shown in Table 6. In general, E2.1 (with SAMP-11) and E2.2 (with SAMP-12) showed a better balance of adhesion (before and after aging) and cure / physical properties (e.g., state of cure, green tear strength and tensile strength after cure, and tensile strength and elongation after oil aging) than the control samples (C2.1-C2.6).
[0399] Table 6: Hose Compound Properties
[0400]
[0401] Table 7 shows the properties of the tape compounds. In general, E3.1 and E3.2 showed a better balance of adhesion and cure / physical properties (e.g., state of cure, hardness, tensile strength, modulus, and tear strength after cure) than C3.1 and C3.2.
[0402] Table 7: Tape Compound Properties
[0403]
[0404] Table 8 shows the properties of tape compounds based on V2504. In general, E4.1, E4.2, E4.4 and E4.5 show a better balance of adhesion and cure / physical properties (e.g., cure state, tensile strength, modulus and tear strength) than C4.1, C4.2 and C4.3. In particular, E4.1 and E4.2 with PEDM-11 generally show the best adhesion improvement and good physical property retention. In addition, E4.3 and E4.6 generally show better cure and physical properties than C4.4 at 100 PEDM loading.
[0405] Table 8: Tape Compound Properties
[0406]
[0407] *There were challenges in preparing good samples of C4.4, E4.3 and E4.6 for quantitative green bond testing, but they all showed significant bond as assessed qualitatively by hand
[0408] Table 9 shows the properties of the hose compounds. In general, E5.1, E5.2, E5.3, and E5.4 show a better balance of adhesion and cure / physical properties (e.g., green strength (stress @ 10% and 25% strain), green tear strength, cured state, tensile strength, modulus, tear strength after cure, and tensile and elongation after oil aging) than C5.1, C5.2, and C5.3. In particular, E5.3 and E5.4 containing Samp-4 generally show the best balance of adhesion and physical properties. In addition, E5.1, E5.2, E5.3, and E5.4 show better compression set than C5.1.
[0409] Table 9: Hose compound properties
[0410]
[0411]
[0412] Table 10 shows the inclusion of two PEDM polymers in place of Vistalon TM Properties of other tape compounds with 706 EPDM. Adhesion improvements are generally observed when PEDM blends are incorporated into the compound. Generally, the adhesion improvements are higher at higher PEDM loadings, and there is a balance between adhesion improvements and cure / physical properties (e.g., state of cure and tear strength after cure).
[0413] Table 10: Tape Compound Properties
[0414]
[0415]
[0416] Table 11 shows the adhesion of rubber to common polar substrates, polycarbonate, aluminum, and stainless steel for EPDM tape and hose compounds containing PEDM. In general, the adhesion of rubber to polar substrates improves with the incorporation of PEDM.
[0417] Table 11: Rubber Adhesion to Polar Substrates for Webbing and Hose Compounds
[0418]
[0419] a The residence time is 4 minutes
[0420] b At the detection limit
[0421] Table 12 shows the properties of the roofing compounds. In general, the compounds with PEDM (E12.1-E12.9) showed performance exceeding Vistalon TM 9301 control compound (C12.1). In particular, E12.7, E12.8, and E12.9 containing Samp-14 showed the best adhesion improvement. TM The compounds containing PEDM showed better retention of cure state, hardness and tensile strength compared to the control compounds (C12.2-C12.4) with 1102.
[0422]
[0423] All documents described herein, including any priority documents and / or test procedures are incorporated by reference in all jurisdictions not inconsistent with the present invention. It is apparent from the above overview and specific embodiments that, although some embodiments have been illustrated and described, various modifications can be made without departing from the spirit and scope of the present disclosure. Therefore, it is not desired that the present disclosure be limited in this manner. Likewise, the term "comprising" is considered synonymous with the term "including". Likewise, whenever a composition, element, or group of elements is preceded by the transitional term "comprising", it should be understood that the same composition or group of elements with the transitional term "essentially consisting of", "consisting of", "selected from", or "is" in front of the listed composition, element, or each element, and vice versa.
Claims
1. An elastomeric composition comprising: 1 to 75 phr of a first propylene-α-olefin-diene (PEDM) terpolymer, the first propylene-α-olefin-diene (PEDM) terpolymer comprising 70 wt% to 79 wt% propylene, 7.5 wt% to 30 wt% C2 or C4-C12 α-olefin and 4 wt% to 8 wt% diene, the wt% being based on the weight of the PEDM terpolymer, wherein the wt% values are represented by 13 C NMR or 1 HNMR measurements; wherein the PEDM terpolymer has a Mooney viscosity ML (1+4) at 125°C + / - 10°C of 25MU to 100MU; and 20 to 99 phr of an ethylene-based copolymer, the ethylene-based copolymer comprising 40 to 95 wt% ethylene, 0 to 10 wt% of one or more dienes, and 5 to 60 wt% of a C3-C12 alpha-olefin, the wt% being based on the total weight of the ethylene-based copolymer, wherein the wt% values are expressed by 13 C NMR or 1 H NMR measurements; Wherein phr means parts by weight per 100 parts by weight of rubber, wherein rubber is the combined weight of PEDM and the ethylene-based copolymer.
2. The elastomeric composition of claim 1, further comprising 1 to 90 phr of a second PEDM terpolymer comprising 1 to 7 wt% of a C2 or C4-12 α-olefin, 93 to 99 wt% of propylene and 0.5 to 7.5 wt% of a diene, and a Mooney viscosity ML (1+4) at 125°C + / - 10°C of 10 to 50 MU.
3. The elastomeric composition of claim 1 further comprising a second PEDM terpolymer.
4. The elastomeric composition of claim 1 wherein said first PEDM terpolymer comprises from 10 wt% to 30 wt% of an alpha-olefin, and from 4 wt% to 8 wt% of a diene.
5. The elastomeric composition of claim 1 wherein said first PEDM terpolymer comprises from 21 wt% to 30 wt% of an alpha-olefin, and from 4 wt% to 8 wt% of a diene.
6. The elastomeric composition of claim 1, wherein the first PEDM terpolymer has a Mooney viscosity ML (1+4) at 125°C + / - 10°C of 30 to 100 MU.
7. The elastomeric composition of claim 1, wherein the first PEDM terpolymer has a Mooney viscosity ML (1+4) at 125°C + / - 10°C of 61 to 100 MU.
8. The elastomeric composition of claim 1 further comprising from 5 to 200 phr of oil.
9. The elastomeric composition of claim 1 further comprising 20 to 200 phr of oil.
10. The elastomeric composition of claim 1, wherein said first PEDM terpolymer has a polymer Tg°C greater than or equal to -7.386-(87.98×E)+(294×D) and less than or equal to -1.386-(87.98×E)+(294×D), wherein E is the mole fraction of ethylene in said polymer and D is the mole fraction of diene in said polymer.
11. The elastomeric composition of claim 1 wherein said first PEDM terpolymer has a heat of fusion (Hf) of less than 1 J / g.
12. The elastomeric composition of claim 1 wherein said first PEDM terpolymer has a number average molecular weight of from 30,000 g / mol to 300,000 g / mol.
13. The elastomeric composition of claim 1 wherein said first PEDM terpolymer has a weight average molecular weight of from 60,000 g / mol to 600,000 g / mol.
14. The elastomeric composition of claim 1 wherein said first PEDM terpolymer has a polydispersity index of from 1.8 to 3.
5.
15. The elastomeric composition of any one of claims 1 to 14, wherein the composition has a rubber-to-rubber adhesion of 20 g-force / inch-width or greater as measured by modified ASTM D3330 / D330M-04 (2010) Methods B and F.
16. The elastomeric composition of any one of claims 1 to 14, wherein the composition has a rubber-to-rubber adhesion of 20 g-force / inch-width to 6000 g-force / inch-width as measured by modified ASTM D3330 / D330M-04 (2010) Methods B and F.
17. The elastomeric composition of any one of claims 1 to 14, wherein the composition has a rubber-to-rubber adhesion of 20 g-force / inch-width or greater after aging for 1 month at room temperature, as measured by modified ASTM D3330 / D330M-04 (2010) Methods B and F.
18. The elastomeric composition of any one of claims 1 to 14, wherein the composition has a rubber-to-rubber adhesion after aging for 1 month at room temperature of 20 g-force / inch-width or greater to 6000 g-force / inch-width as measured by modified ASTM D3330 / D330M-04 (2010) Methods B and F.
19. The elastomeric composition of any one of claims 1-14, wherein the composition has a percent retention of raw rubber to rubber adhesion from blending to aging for one month at room temperature, as measured by modified ASTM D3330 / D330M-04 (2010) Methods B and F, of 20% to 250%.
20. The elastomeric composition of any one of claims 1-14, wherein the composition has a percent retention of raw rubber to rubber adhesion from blending to aging for one month at room temperature, as measured by modified ASTM D3330 / D330M-04 (2010) Methods B and F, of 50% to 250%.
21. The elastomeric composition of any one of claims 1 to 14, wherein the composition is secured to a polar substrate, wherein the composition has a rubber to polar substrate adhesion of 10 g-force / inch width or greater, wherein the polar substrate is selected from the group consisting of cotton, rayon, polyamide, polyester, stainless steel, aluminum, polyketone, and polycarbonate, as measured by modified ASTM D3330 / D330M-04 (2010) Methods B and F.
22. The elastomeric composition of claim 21 wherein said polyamide is an aromatic polyamide.
23. The elastomeric composition of any one of claims 1 to 14, wherein the composition is attached to a polar substrate, wherein the composition has a rubber to polar substrate adhesion of 10 g-force / inch-width to 500 g-force / inch-width, wherein the polar substrate is selected from the group consisting of cotton, rayon, polyamide, polyester, stainless steel, aluminum, polyketone, and polycarbonate, as measured by modified ASTM D3330 / D330M-04 (2010) Methods B and F.
24. The elastomeric composition of claim 23, wherein the polyamide is an aromatic polyamide.
25. An at least partially crosslinked elastomeric composition which is the reaction product of: The elastomeric composition according to any one of claims 1 to 24; one or more vulcanization activators; and One or more vulcanizing agents.
26. A belt comprising: an elastomeric composition according to any one of claims 1 to 24.
27. A hose comprising: an elastomeric composition according to any one of claims 1 to 24.
28. A roof membrane comprising: an elastomeric composition according to any one of claims 1 to 24.
29. A composition comprising:
24. The elastomeric composition of claim 1 adhered to at least one polyester substrate selected from the group consisting of polyester films, polyester woven fabrics and polyester nonwoven fabrics.
30. The composition of claim 29, wherein the polyester woven fabric is a polyester cord.
31. A composition comprising:
24. The elastomeric composition of claim 1 adhered to at least one substrate selected from the group consisting of cotton, rayon, polyamide, polyester, polycarbonate, steel, aluminum, glass, carbon, polyketone, basalt, boron and discontinuous fibers.
32. The composition of claim 31 wherein the polyamide is an aromatic polyamide.
33. The composition of any one of claims 29-32, wherein the substrate comprises a treated surface.
34. The composition of claim 33, wherein said treated surface comprises a physically bonded coating on said substrate.
35. The composition of claim 33, wherein said treated surface comprises a chemically bonded coating on said substrate.
36. The composition of claim 34, wherein said coating comprises said first PEDM terpolymer.
37. The composition of claim 35, wherein said coating comprises said first PEDM terpolymer.
38. A composition comprising:
24. An elastomeric composition according to any one of claims 1 to 24 adhered to a polyamide substrate.
Citation Information
Patent Citations
Process for producing a catalyst system, process for the (co)polymerization of olefins and (co)polymers of at least one olefin
EP0573120B1
Graft-modified polymers based on novel propylene ethylene copolymers
US20040054086A1
Polychromatic imaging method
US20130050488A1
Expansible thermoplastic polymer particles containing volatile fluid foaming agent and method of foaming the same
US3615972A
Easy processing ethylene propylene elastomers
US4722971A